Polyethylene composition and film comprising same
By developing a polyethylene composition containing ethylene-α olefin copolymer, optimizing its high crystallinity and medium crystallinity molecular fraction, the problem of insufficient mechanical properties in film production of LLDPE resin is solved, and a polyethylene film with excellent mechanical properties and high initial modulus is achieved.
Patent Information
- Application Number
- CN202380074563.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-08
- Filing Date
- 2023-11-02
- Publication Date
- 2025-06-13
AI Technical Summary
The existing LLDPE resins lack mechanical properties and lack rigidity during film production, and cannot effectively replace film materials such as nylon and PET, which limits the development of renewable packaging materials.
A polyethylene composition is developed that comprises at least one ethylene-alpha olefin copolymer, and the balance between mechanical properties and membrane processability is controlled by optimization of high crystallinity molecular fraction and medium crystallinity molecular fraction analyzed by TREF.
The preparation of polyethylene films with excellent mechanical properties and high initial modulus is achieved, maintaining printing suitability, transparency, productivity and film processing, and is suitable for packaging and industrial lining.
Smart Images

Figure BDA0005370087190000101 
Figure BDA0005370087190000131 
Figure BDA0005370087190000151
Abstract
Description
[0001] Cross - reference to related applications
[0002] This application claims the benefit of Korean Patent Application Nos. 10 - 2022 - 0144633, filed on November 2, 2022, 10 - 2022 - 0170467, filed on December 8, 2022, and 10 - 2023 - 0150130, filed on November 2, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety. Technical field
[0003] The present invention relates to a polyethylene composition suitable for a polyethylene film, which has high initial modulus and excellent rigidity while maintaining excellent printability, transparency, productivity, and film processability, and to a polyethylene film comprising the polyethylene composition. Background art
[0004] Film products made of linear low - density polyethylene (LLDPE) and / or high - density polyethylene (HDPE) are widely used for packaging (such as merchandise bags, shopping bags, food, and special product packaging) and industrial liners. In these applications, shrink films that can package goods while maintaining their shape are mainly used to prevent products from being touched during display.
[0005] In particular, linear low - density polyethylene (LLDPE) is flexible and has suitable impact resistance and processability, making it widely used as a PE resin for films. Linear low - density polyethylene films (LLDPE films) are produced by methods such as blow - molding, casting, and biaxial stretching, and are used for packaging materials, shrink films, and agricultural films. Recently, biaxially oriented LLDPE films have been developed and applied to improve the mechanical properties of the films and achieve thinning. In addition, since commercially available packaging films are composite materials composed of polyethylene (PE) resin and other resins, efforts are being made to develop renewable all - PE packaging materials that can replace other film layers composed of resins such as polyamide (nylon) and polyethylene terephthalate (PET).
[0006] However, compared with HDPE resin, commercial LLDPE resins have relatively low crystallinity and density, showing deficiencies in mechanical properties during film production, which limits their applications. In particular, compared with other film materials such as nylon and PET, it lacks rigidity, making it unable to effectively serve as a substitute and restricting the development of renewable packaging materials.
[0007] Therefore, there is a need for a polyethylene composition having high crystallinity and density, which has the characteristics and processability of LLDPE and is suitable for films exhibiting excellent mechanical properties. Summary of the Invention
[0008] Technical Problem
[0009] The present invention relates to a polyethylene composition capable of preparing a polyethylene film having excellent rigidity due to excellent mechanical properties, the polyethylene film having high tensile strength and initial modulus while maintaining excellent printability, transparency, productivity, and film processability, and to a film containing the polyethylene composition.
[0010] Technical Solution
[0011] According to an embodiment of the present invention, there is provided a polyethylene composition comprising at least one ethylene-α-olefin copolymer, wherein the molecular fraction eluted above 90 °C from TREF analysis (TREF ≥90℃ ) of the polyethylene composition is 55.0% or more, and the molecular fraction eluted above 35 °C and less than 90 °C from TREF analysis (TREF 35-90℃ ) is 45% or less.
[0012] In another embodiment of the present invention, there is provided a polyethylene film comprising the polyethylene composition of the above embodiment.
[0013] The terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the present invention.
[0014] The singular forms are also intended to include the plural forms unless the context clearly dictates otherwise.
[0015] In the present invention, the terms "comprising", "including" or "having" are used to describe the features, quantities, steps, components or combinations thereof, and do not exclude the addition of one or more other features, quantities, steps, components or combinations thereof.
[0016] The term "about" or "substantially" is intended to have a meaning similar to a numerical value or range specified with an allowable error, and is intended to prevent the exact or absolute numerical value disclosed for understanding the present invention from being illegally or unjustly used by any unreasonable third party.
[0017] Furthermore, in the present invention, (co)polymers are intended to include homopolymers and copolymers.
[0018] Unless otherwise defined herein, "copolymerization" may mean block copolymerization, random copolymerization, graft copolymerization or alternating copolymerization, and "copolymer" means block copolymer, random copolymer, graft copolymer or alternating copolymer.
[0019] Since various modifications can be made to the present invention and the present invention has various forms, specific embodiments thereof are shown by way of example and will be described in detail. However, it is not intended to limit the present invention to the specific forms disclosed, and it should be understood that the present invention includes all modifications, equivalents, and alternative forms within the spirit and technical scope of the present invention.
[0020] Hereinafter, the present invention will be described in more detail.
[0021] Polyethylene composition
[0022] According to one aspect of the present invention, a polyethylene composition is provided, which comprises at least one ethylene-α-olefin copolymer, wherein the molecular fraction eluting above 90 °C from TREF analysis of the polyethylene composition (TREF ≥90℃ ) is 55.0% or more, and the molecular fraction eluting above 35 °C and less than 90 °C from TREF analysis of the polyethylene composition (TREF 35-90℃ ) is 45% or less.
[0023] In addition, "parts by weight" used herein refers to a relative concept of the ratio of the weight of the remaining materials based on the weight of a specific material. For example, in a mixture containing 50 g of material A, 20 g of material B, and 30 g of material C, based on 100 parts by weight of material A, the amounts of materials B and C are 40 parts by weight and 60 parts by weight, respectively.
[0024] Meanwhile, "wt%" refers to an absolute concept of the weight of a specific material expressed as a percentage based on the total weight. In the above mixture, based on the total weight of 100% of the mixture, the contents of materials A, B, and C are 50 wt%, 20 wt%, and 30 wt%, respectively.
[0025] In the polyethylene composition of the present invention, a first ethylene-α-olefin copolymer having excellent mechanical properties is blended with a second ethylene-α-olefin copolymer having excellent fluidity to impart stretchability by applying specific metallocene catalysts described hereinafter, respectively. By optimizing the first and second ethylene-α-olefin copolymers at a predetermined content ratio, the balance between mechanical properties and film processability is effectively controlled. Therefore, it has characteristics suitable for manufacturing a polyethylene film, which has excellent mechanical properties by having high tensile strength and initial modulus while maintaining printing suitability, transparency, productivity, and film processability equivalent to or superior to conventional materials.
[0026] The content ratio of the highly crystalline fraction eluting above 90 °C from cross-fractionation chromatography (CFC) analysis of the polyethylene composition (TREF ≥90℃) is more than 55.0% or more than 55.0% and 95% or less of the total weight of all the eluted fractions. Specifically, the content ratio (TREF ≥90℃ ) can be more than 57%, more than 58%, more than 59%, more than 59.5%, more than 60%, more than 60.5%, more than 61%, more than 61.5%, more than 62%, more than 62.5%, more than 63%, more than 63.5%, more than 64%, or more than 66% of the total weight of all the eluted fractions, and, if necessary, can be 93% or less, 90% or less, 88% or less, 85% or less, 82% or less, 80% or less, 79.5% or less, 79% or less, or 78.5% or less of the total weight of all the eluted fractions.
[0027] In the polyethylene composition, when analyzed by cross fractionation chromatography (CFC), the content ratio (TREF 35-90℃ ) of the medium-crystallinity fraction eluted at 35°C or higher and less than 90°C can be 45.0% or less, or 10% or more and 45.0% or less of the total weight of all the eluted fractions. Specifically, the content ratio (TREF 35-90℃ ) can be 44.9% or less, 44% or less, 43% or less, 42% or less, 41% or less, 40% or less, 39.5% or less, 39% or less, 38.5% or less, 38% or less, 37% or less, 36% or less, 35% or less, 34% or less, 33.5% or less, 33% or less, 32.5% or less, or 32.1% or less of the total weight of all the eluted fractions, and can be 12% or more, 12.5% or more, 13% or more, 13.5% or more, 15% or more, 15.5% or more, 16% or more, 17% or more, 18% or more, 18.5% or more, 18.8% or more, 19% or more, 20% or more, or 21% or more of the total weight of all the eluted fractions.
[0028] In the polyethylene composition, when analyzed by cross fractionation chromatography (CFC), the content ratio (TREF <35℃ ) of the soluble fraction eluted at lower than 35°C can be 3.0% or less, or 0.1% or more and 3.0% or less of the total weight of all the eluted fractions. Specifically, the content ratio (TREF <35℃) may be 2.9% or less, 2.8% or less, 2.7% or less, 2.6% or less, 2.5% or less, 2.4% or less, 2.3% or less, 2.2% or less, 2.1% or less, 2.0% or less, or 1.9% or less of the total weight of all eluted fractions, and when necessary, may be 0.1% or more, 0.15% or more, 0.2% or more, 0.25% or more, 0.3% or more, 0.35% or more, 0.4% or more, 0.45% or more, 0.5% or more, 0.55% or more, 0.6% or more, 0.65% or more, 0.7% or more, 0.75% or more, or 0.8% or more of the total weight of all eluted fractions.
[0029] In addition, in the polyethylene composition, when analyzed by cross fractionation chromatography (CFC), the content ratio of the highly crystalline fraction eluted at 90 °C or higher (TREF ≥90℃ ), the content ratio of the medium crystalline fraction eluted at 35 °C or higher and less than 90 °C (TREF 35-90℃ ), and the content ratio of the non-crystalline fraction eluted at less than 35 °C (i.e., the content ratio of the soluble fraction) (TREF <35℃ ) are set within the range where the sum of the highly crystalline fraction, the medium crystalline fraction, and the non-crystalline fraction does not exceed 100%.
[0030] In the present invention, the specific test method related to cross fractionation chromatography (CFC) is as described in Test Example 2 below. However, cross fractionation chromatography (CFC) is not limited thereto, and can be measured by other methods known in the art to which the present invention pertains.
[0031] Meanwhile, the density of the polyethylene composition may be 0.925 g / cm 3 or more and 0.945 g / cm 3 or less. Preferably, the density may be 0.930 g / cm 3 or more, or 0.935 g / cm 3 or more, or 0.937 g / cm 3 or more, and may be 0.944 g / cm 3 or less, or 0.943 g / cm 3 or less, or 0.942 g / cm 3 or less, or 0.941 g / cm 3 or less, or 0.940 g / cm 3 or less.
[0032] In the present invention, the density (g / cm 3 ) can be measured according to ASTM D 1505 (American Society for Testing and Materials) by using a density gradient column. For example, the density (g / cm 3) The testing method is as described in Test Examples 1 and 2 which will be described below.
[0033] In addition, the melt index (MI 2.16 , at 190 °C, under a load of 2.16 kg) can be from 0.18 g / 10 min to 1.5 g / 10 min. Preferably, the melt index (MI 2.16 , at 190 °C, under a load of 2.16 kg) can be more than 0.2 g / 10 min, or more than 0.3 g / 10 min, or more than 0.4 g / 10 min, or more than 0.5 g / 10 min, or more than 0.6 g / 10 min, and can be 1.3 g / 10 min or less, or 1.1 g / 10 min or less, or 1.0 g / 10 min or less, or 0.9 g / 10 min or less, or 0.8 g / 10 min or less.
[0034] In the present invention, the melt index (MI 2.16 ) can be measured at 190 °C under a load of 2.16 kg according to ASTM D 1238 (Condition E, 190 °C, 2.16 kg) of the American Society for Testing and Materials. For example, the measuring method of the melt index (MI 2.16 ) is as described in Test Examples 1 and 2 which will be described below.
[0035] In addition, the number-average molecular weight (Mn) of the polyethylene composition can be 18500 g / mol or more, or 18800 g / mol or more, or 19000 g / mol or more, or 19500 g / mol or more, or 20000 g / mol or more, or 25000 g / mol or more, 28000 g / mol or more, or 30000 g / mol or more, or 31000 g / mol or more, and can be 100000 g / mol or less, or 70000 g / mol or less, or 50000 g / mol or less, or 40000 g / mol or less, or 35000 g / mol or less, or 34000 g / mol or less. The weight-average molecular weight (Mw) of the polyethylene composition can be 100000 g / mol or more, or 105000 g / mol or more, or 110000 g / mol or more, and can be 500000 g / mol or less, or 400000 g / mol or less, or 300000 g / mol or less, or 200000 g / mol or less, or 180000 g / mol or less, or 160000 g / mol or less, or 140000 g / mol or less, or 120000 g / mol or less, or 116000 g / mol or less, or 114000 g / mol or less.
[0036] The molecular weight distribution (Mw / Mn) of the polyethylene composition can be 9.5 or less, or 9.0 or less, or 8.0 or less, or 6.0 or less, or 5.0 or less, or 4.0 or less, or 3.8 or less, or 3.7 or less.
[0037] In the present invention, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are values converted from standard polystyrene measured by GPC (gel permeation chromatography). However, the weight-average molecular weight is not limited thereto and can be measured by other methods known in the art. As an example, the measurement methods of the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are as described in Test Examples 1 and 2 to be described below.
[0038] In addition, the melting point (Tm) of the polyethylene composition can be 127 °C or higher and 130 °C or lower, or 127.2 °C or higher and 129.8 °C or lower, or 127.5 °C or higher and 129.5 °C or higher, or 128.5 °C or higher and 128.7 °C or lower. The crystallization temperature (Tc) of the polyethylene composition can be 110 °C or higher and 115 °C or lower, or 111 °C or higher and 114.8 °C or lower, or 111.5 °C or higher and 114.5 °C or lower, or 111.6 °C or higher and 113.85 °C or lower. The crystallinity (Xc) of the polyethylene composition can be 50% or higher and 70% or lower, or 52% or higher and 69.8% or lower, or 55% or higher and 69.5% or lower, or 58% or higher and 69% or lower, or 60% or higher and 68.5% or lower.
[0039] Preferably, the melting point can be 128.0 °C or higher, and can be 129.0 °C or lower, or 128.6 °C or lower. The crystallization temperature can be 111.6 °C or higher, and can be 114 °C or lower, 113 °C or lower, or 112.3 °C or lower. The crystallinity can be 55% or higher, or 58% or higher, or 60% or higher, or 60.1% or higher, and can be 69% or lower, or 68.4% or lower.
[0040] In the present invention, the melting point Tm, the crystallization temperature Tc, and the crystallinity Xc can be measured using a differential scanning calorimeter (DSC, for example, equipment name: DSC Q20, manufacturer: TA instrument). For example, the measurement methods of the melting point Tm, the crystallization temperature Tc, and the crystallinity Xc are as described in Test Example 2 to be described below.
[0041] Meanwhile, the polyethylene composition of the present invention exhibits high yield strength and secant modulus (i.e., 1% and 2% initial moduli), indicating excellent mechanical properties.
[0042] Specifically, the yield strength of the polyethylene composition measured according to ASTM D 638 standard can be 18 MPa or more, or 18.2 MPa or more, or 18.5 MPa or more, or 18.8 MPa or more, or 19 MPa or more, or 19.5 MPa or more, or 20 MPa or more, or 20.5 MPa, or 20.8 MPa or more, and can be 100 MPa or less. Herein, the yield strength is the strength at the yield point.
[0043] For example, by performing a tensile test on the polyethylene composition
[0044] Compression molding is carried out at a temperature of 180 °C and a pressure of 4500 lbf for 15 minutes to produce a sheet with a thickness of 1 mm. Subsequently, tensile specimens are prepared according to ASTM D 638 standard, and the specimens are tested at a tensile rate of 500% / minute at room temperature (20 °C to 25 °C) according to ASTM D 638 standard. The specific test method for the yield strength is as described in Test Example 2 below.
[0045] As indicated by the high initial modulus measured according to ASTM D 638 standard (i.e., the high range of 1% modulus and 2% modulus, which are the initial moduli at 1% and 2% elongation on the strength-elongation curve obtained from the tensile test according to ASTM D 638 standard), the polyethylene composition has excellent stiffness. Specifically, the 1% modulus of the polyethylene composition can be 400 MPa or more, or 420 MPa or more, or 450 MPa or more, or 480 MPa or more, or 500 MPa or more, or 520 MPa or more, or 550 MPa or more, or 580 MPa or more, or 600 MPa or more, or 605 MPa or more, and can be 1100 MPa or less. The 2% modulus of the polyethylene composition can be 330 MPa or more, or 340 MPa or more, or 350 MPa or more, or 375 MPa or more, or 400 MPa or more, or 420 MPa or more, or 450 MPa or more, or 480 MPa or more, or 500 MPa or more, or 505 MPa or more, and can be 1000 MPa or less. Herein, the 1% modulus and 2% modulus respectively refer to the modulus values at 1% and 2% elongation on the strength-elongation curve obtained from the tensile test as described above.
[0046] In addition, the tensile strength of the polyethylene composition measured according to ASTM D 638 standard can be 32 MPa or more, or 32.5 MPa or more, or 33 MPa or more, or 33.5 MPa or more, or 34 MPa or more, or 34.5 MPa or more, or 35 MPa or more, or 35.5 MPa or more, or 36 MPa or more, or 36.2 MPa or more, or 36.6 MPa or more, and can be 100 MPa or less. Herein, the tensile strength refers to the strength at the breaking point in the tensile test as described above.
[0047] The elongation at break of the polyethylene composition measured according to ASTM D 638 standard can be 625% or more and 785% or less, or 630% or more and 780% or less, or 640% or more and 775% or less, or 650% or more and 770% or less, or 670% or more and 765% or less, or 690% or more and 760% or less, or 695% or more and 730% or less, or 700% or more and 720% or less. Herein, the elongation at break refers to the elongation at the breaking point in the tensile test as described above.
[0048] Meanwhile, one embodiment of the present invention includes (a) a first ethylene-α-olefin copolymer having a density of 0.930 g / cm 3 to 0.960 g / cm 3 and a melt index (MI 2.16 , under a load of 2.16 kg at 190 °C) of 0.05 g / 10 min or more; and (b) a second ethylene-α-olefin copolymer having a density of 0.870 g / cm 3 to 0.920 g / cm 3 and a melt index (MI 2.16 , under a load of 2.16 kg at 190 °C) of 15 g / 10 min or more; and
[0049] Specifically, the polyethylene composition of one embodiment of the present invention contains (a) the first ethylene-α-olefin copolymer in an amount of 82% by weight or more and less than 100% by weight, and (b) the second ethylene-α-olefin copolymer in an amount of more than 0% by weight and 18% by weight or less. In the polyethylene composition of the present invention, the first ethylene-α-olefin copolymer having excellent mechanical properties is blended with the second ethylene-α-olefin copolymer having excellent fluidity to impart stretchability, thereby adjusting the balance between mechanical properties and elongation. Therefore, it has characteristics suitable for manufacturing a polyethylene film, which has high shrink resistance, printability, and transparency while maintaining mechanical properties, productivity, and tensile stability equivalent to or better than conventional materials.
[0050] Preferably, the content of the (a) first ethylene-α-olefin copolymer may be 83% by weight or more, or 84% by weight or more, or 85% by weight or more, and may be 99% by weight or less, 97% by weight or less, or 95% by weight or less.
[0051] In addition, the content of the (b) second ethylene-α-olefin copolymer may be 1% by weight or more, or 3% by weight or more, or 5% by weight or more, and may be 17% by weight or less, or 16% by weight or less, or 15% by weight or less.
[0052] For example, the content of the (a) first ethylene-α-olefin copolymer may be 82% by weight or more and 97% by weight or less, and the content of the (b) second ethylene-α-olefin copolymer may be 3% by weight or more and 18% by weight or less.
[0053] Meanwhile, the (a) first ethylene-α-olefin copolymer may be 4 times or more, or 4 times or more and 100 times or less by weight based on the (b) second ethylene-α-olefin copolymer.
[0054] For example, the (a) first ethylene-α-olefin copolymer may be 4 times or more, or 4.2 times or more, or 4.4 times or more, or 4.5 times or more, or 5 times or more, or 5.2 times or more, or 5.4 times or more, or 5.5 times or more, or 5.6 times or more, and may be 99 times or less, or 80 times or less, or 50 times or less, or 40 times or less, or 35 times or less, or 33 times or less, or 30 times or less, or 28 times or less, or 25 times or less, or 22 times or less, or 20 times or less, or 19 times or less, or 15 times or less, or 12 times or less, or 10 times or less, or 9 times or less.
[0055] In the polyethylene copolymer of an embodiment of the present invention, the (a) first ethylene-α-olefin copolymer may be an ethylene / 1-hexene copolymer, and the (b) second ethylene-α-olefin copolymer may be an ethylene / 1-octene copolymer.
[0056] (a) First ethylene-α-olefin copolymer
[0057] In the polyethylene composition of an embodiment of the present invention, the (a) first ethylene-α-olefin copolymer has excellent mechanical properties and an appropriate balance between crystallinity and processability, thereby imparting characteristics suitable for manufacturing a polyethylene film having a consistent elongation rate and high mechanical properties.
[0058] Specifically, the density of the (a) first ethylene-α-olefin copolymer may be 0.930 g / cm 3 to 0.960 g / cm 3 and the melt index (MI 2.16, at 190 °C and a load of 2.16 kg) can be 0.05 g / 10 min or more, or 0.05 g / 10 min to 2.0 g / 10 min.
[0059] Preferably, (a) the density of the first ethylene-α-olefin copolymer can be 0.933 g / cm 3 or more, or 0.935 g / cm 3 or more, or 0.938 g / cm 3 or more, or 0.941 g / cm 3 or more, and can be 0.955 g / cm 3 or less, or 0.950 g / cm 3 or less, or 0.948 g / cm 3 or less.
[0060] (a) The melt index (MI 2.16 , at 190 °C and a load of 2.16 kg) can be 0.05 g / 10 min or more, or 0.1 g / 10 min or more, or 0.15 g / 10 min or more, or 0.17 g / 10 min or more, or 0.2 g / 10 min or more. In terms of ensuring excellent mechanical properties, high tensile strength and initial modulus during film processing, (a) the melt index (MI 2.16 , at 190 °C and a load of 2.16 kg) can be 1.8 g / 10 min or less, or 1.5 g / 10 min or less, or 1.2 g / 10 min or less, or 1.0 g / 10 min or less, or 0.8 g / 10 min or less, or 0.6 g / 10 min or less.
[0061] In addition, (a) the number-average molecular weight (Mn) of the first ethylene-α-olefin copolymer can be 12,000 g / mol or more and 50,000 g / mol or less, the weight-average molecular weight (Mw) can be 80,000 g / mol or more and 250,000 g / mol or less, and the molecular weight distribution (Mw / Mn) can be 3.0 or more and 20.0 or less.
[0062] Preferably, (a) the number-average molecular weight (Mn) of the first ethylene-α-olefin copolymer can be 13,000 g / mol or more, or 14,000 g / mol or more, or 15,000 g / mol or more, and can be 40,000 g / mol or less, or 30,000 g / mol or less, or 28,000 g / mol or less.
[0063] (a) The weight average molecular weight (Mw) of the first ethylene-α-olefin copolymer can be 90,000 g / mol or more, or 100,000 g / mol or more, or 114,000 g / mol or more, and can be 230,000 g / mol or less, or 210,000 g / mol or less, or 200,000 g / mol or less.
[0064] (a) The molecular weight distribution (Mw / Mn) of the first ethylene-α-olefin copolymer can be 3.5 or more, or 3.8 or more, or 4.0 or more, or 4.1 or more, and can be 17.0 or less, or 15.0 or less, or 14.0 or less, or 13.1 or less.
[0065] In particular, (a) the first ethylene-α-olefin copolymer can have at least one of the above physical properties, and can have all of the above physical properties to exhibit excellent mechanical strength.
[0066] In the present invention, (a) the first ethylene-α-olefin copolymer can contain at least one α-olefin selected from the group consisting of: 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and mixtures thereof, together with ethylene.
[0067] Preferably, (a) the first ethylene-α-olefin copolymer can be an ethylene / 1-hexene copolymer.
[0068] When (a) the first ethylene-α-olefin copolymer is the above copolymer, the above physical properties can be easily achieved. However, the type of (a) the first ethylene-α-olefin copolymer is not limited thereto, and various types known in the art can be used as long as they can exhibit the above physical properties.
[0069] Meanwhile, (a) the first ethylene-α-olefin copolymer can be prepared in the presence of a metallocene catalyst.
[0070] Specifically, (a) the first ethylene-α-olefin copolymer can be prepared by copolymerizing ethylene and a comonomer while introducing hydrogen in the presence of a catalyst composition containing a first metallocene compound represented by the following Chemical Formula 1 and a second metallocene compound represented by the following Chemical Formula 2 in a molar ratio of 1:1 to 1:8:
[0071] [Chemical Formula 1]
[0072] (Cp 1 R a ) m (Cp 2 R b )M 2 Z 23-m
[0073] In Chemical Formula 1,
[0074] M 2 is a Group 4 transition metal;
[0075] Cp 1 and Cp 2 are each independently an unsubstituted or C 1-20 hydrocarbon-substituted cyclopentadienyl;
[0076] R a and R b are the same as or different from each other and are each independently C 1-20 alkyl, C 1-20 alkoxy, C 2-20 alkoxyalkyl, C 6-20 aryl, C 6-20 aryloxy, C 2-20 alkenyl, C 7-40 alkylaryl, C 7-40 arylalkyl, C 8-40 arylalkenyl, C 2-20 alkynyl, or a substituted or unsubstituted C 2-20 heteroaryl containing at least one heteroatom selected from the group consisting of N, O, and S, provided that at least one of R a and R b is not hydrogen;
[0077] Z 2 are each independently halogen, C 1-20 alkyl, C 2-20 alkenyl, C 7-40 alkylaryl, C 7-40 arylalkyl, C 6-20 aryl, a substituted or unsubstituted C 1-20 alkylidene, a substituted or unsubstituted amino, C 2-20 alkylalkoxy, or C 7-40 arylalkoxy; and
[0078] m is 1 or 0;
[0079] [Chemical Formula 2]
[0080]
[0081] In Chemical Formula 2,
[0082] M 3 is a Group 4 transition metal,
[0083] T 2 is carbon, silicon, or germanium,
[0084] X 3 and X 4 are the same as or different from each other and are each independently a halogen or a C 1-20 alkyl group,
[0085] R 11 to R 14 are the same as or different from each other and are each independently hydrogen, a C 1-20 alkyl group, a C 2-20 alkenyl group, a C 6-20 aryl group, a C 7-20 alkylaryl group, a C 7-20 arylalkyl group, or two or more of the Rs adjacent to each other 11 to R 14 are joined to each other to form a substituted or unsubstituted aliphatic ring, a substituted or unsubstituted aromatic ring, or a substituted or unsubstituted heteroaromatic ring containing at least one selected from the group consisting of N, O, and S,
[0086] Q 3 and Q 4 are the same as or different from each other and are each independently a C 1-20 alkyl group, a C 2-20 alkenyl group, a C 6-30 aryl group, or a C 2-20 alkoxyalkyl group, and
[0087] R 15 is a C 1-20 alkyl group, a C 2-20 alkenyl group, or a C 6-30 aryl group.
[0088] Unless otherwise specified herein, the following terms can be defined as follows.
[0089] Halogen can be fluorine (F), chlorine (Cl), bromine (Br), or iodine (I).
[0090] C 1-20 alkyl group can be a straight-chain, branched, or cyclic alkyl group. Specifically, C 1-20 alkyl group can be a C 1-15 straight-chain alkyl group; a C 1-10 straight-chain alkyl group; a C 1-5 straight-chain alkyl group; a C 3-20 branched or cyclic alkyl group; a C 3-15 branched or cyclic alkyl group; or a C 3-10 branched or cyclic alkyl group. More specifically, C 1-20 alkyl group can be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, cyclohexyl, etc.
[0091] C 2-20The alkenyl group can be linear, branched, or cyclic. Specifically, C 2-20 The alkenyl group can be C 2-20 a linear alkenyl group, C 2-10 a linear alkenyl group, C 2-5 a linear alkenyl group, C 3-20 a branched alkenyl group, C 3-15 a branched alkenyl group, C 3-10 a branched alkenyl group, C 5-20 a cyclic alkenyl group or C 5-10 a cyclic alkenyl group. More specifically, C 2-20 the alkenyl group can be vinyl, propenyl, butenyl, pentenyl, cyclohexenyl, etc.
[0092] C 6-20 The aryl group can be a monocyclic, bicyclic, or tricyclic aromatic hydrocarbon and includes monocyclic or fused-ring aryl groups. Specifically, C 6-20 the aryl group can be phenyl, biphenyl, naphthyl, anthryl, phenanthryl, fluorenyl, etc.
[0093] C 7-40 The alkylaryl group can be a substituent in which at least one hydrogen of the aryl group is substituted by an alkyl group. Specifically, C 7-40 the alkylaryl group can be methylphenyl, ethylphenyl, n-propylphenyl, isopropylphenyl, n-butylphenyl, isobutylphenyl, tert-butylphenyl, cyclohexylphenyl, etc.
[0094] C 7-40 The arylalkyl group can include a substituent in which at least one hydrogen of the alkyl group is substituted by an aryl group. Specifically, C 7-40 the arylalkyl group can be benzyl, phenylpropyl, phenylhexyl, etc.
[0095] C 6-20 The aryloxy group can be phenoxy, biphenyloxy, naphthyloxy, etc., but the present invention is not limited thereto.
[0096] C 1-20 The alkoxy group can be methoxy, ethoxy, phenoxy, cyclohexyloxy, etc., but the present invention is not limited thereto.
[0097] C 2-20 The alkoxyalkyl group is a functional group in which at least one hydrogen of the alkyl group is substituted by an alkoxy group, and specifically, it can be an alkoxyalkyl group, for example, methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl, tert-butoxyhexyl, etc., but the present invention is not limited thereto.
[0098] C 1-20 The alkylsilyl group or C 1-20 the alkoxysilyl group is -SiH 3A functional group in which 1 to 3 hydrogens are substituted by 1 to 3 of the above-mentioned alkyl or alkoxy groups, and specifically, it can be an alkylsilyl group, for example, methylsilyl, dimethylsilyl, trimethylsilyl, dimethylethylsilyl, diethylmethylsilyl or dimethylpropylsilyl; an alkoxysilyl group, for example, methoxysilyl, dimethoxysilyl, trimethoxysilyl or dimethoxyethoxysilyl; or an alkoxyalkylsilyl group, for example, methoxydimethylsilyl, diethoxymethylsilyl or dimethoxypropylsilyl, but the present invention is not limited thereto.
[0099] C 1-20 Silylalkyl is a functional group in which at least one hydrogen of an alkyl group is substituted by a silyl group, and specifically, it can be -CH 2 -SiH 3 , methylsilylmethyl or dimethoxyethylsilylpropyl, etc., but the present invention is not limited thereto.
[0100] The sulfonate group can have a structure of -O-SO 2 -R', where R' can be C 1-20 alkyl. Specifically, the C 1-20 sulfonate group can be a methanesulfonate group, a phenylsulfonate group, etc.
[0101] A heteroaryl group is a C 2-20 heteroaryl group containing at least one of N, O and S as a hetero element, and includes a monocyclic or fused-ring heteroaryl group. Specifically, it can be xanthinyl, thioxanthenyl, thienyl, furyl, pyrrolyl, imidazolyl, thiazolyl, oxazolyl, oxadiazolyl, triazolyl, pyridyl, bipyridyl, pyrimidinyl, triazinyl, acridinyl, pyrazolyl, pyrazinyl, quinolinyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, pyrazinopyrazinyl, isoquinolinyl, indolyl, carbazolyl, benzoxazolyl, benzimidazolyl, benzothiazolyl, benzocarbazolyl, benzothienyl, dibenzothienyl, benzofuryl, phenanthrolinyl, isoxazolyl, thiadiazolyl, phenothiazinyl, dibenzofuryl, etc., but the present invention is not limited thereto.
[0102] In addition, the Group 4 transition metal can be titanium (Ti), zirconium (Zr), hafnium (Hf) or (Rf), and specifically is titanium (Ti), zirconium (Zr) and hafnium (Hf). More specifically, it can be zirconium (Zr) or hafnium (Hf), but is not limited thereto.
[0103] In addition, the Group 13 element can be boron (B), aluminum (Al), gallium (Ga), indium (In) or thallium (Tl), and specifically is boron (B) or aluminum (Al), but is not limited thereto.
[0104] The above substituents may optionally be substituted with one or more substituents selected from the group consisting of: a hydroxyl group; a halogen; an alkyl or alkenyl, aryl, alkoxy group; an alkyl or alkenyl, aryl, alkoxy group containing at least one heteroatom of Group 14 to Group 16 heteroatoms; a silyl group; an alkylsilyl or alkoxysilyl group; a phosphino group; a phosphide group; a sulfonate group; and a sulfone group within the range of exhibiting the same or similar effects as the desired effect.
[0105] In addition, "two adjacent substituents are connected to each other to form an aliphatic ring or an aromatic ring" means that the atoms of the two substituents and the atoms bonded to the two substituents are connected to each other to form a ring. Specifically, -NR 9 R 10 For R 9 and R 10 Examples of forming an aliphatic ring by connecting to each other include a piperidyl group, -NR 9 R 10 For R 9 and R 10 Examples of forming an aromatic ring by connecting to each other include a pyrrolyl group.
[0106] In the catalyst composition, the first metallocene compound represented by Chemical Formula 1 is a non-crosslinked compound containing ligands Cp 1 and Cp 2 and is favorable for mainly producing a low molecular weight copolymer with a low SCB (short chain branch) content.
[0107] Specifically, in Chemical Formula 1, the ligands Cp 1 and Cp 2 may be the same as or different from each other, and may each be a cyclopentadienyl group and substituted with one or more or one to three C 1-10 alkyl groups. Since the ligands Cp 1 and Cp 2 have a pair of non-covalent electrons capable of acting as a Lewis base, high polymerization activity can be achieved. In particular, since the ligands Cp 1 and Cp 2 are cyclopentadienyl groups with relatively low steric hindrance, they exhibit high polymerization activity and low hydrogen reactivity, and thus can polymerize low molecular weight polyethylene with high activity.
[0108] In addition, the ligands Cp 1 and Cp 2 can easily control the properties such as chemical structure, molecular weight, molecular weight distribution, mechanical properties, and transparency of the polyethylene to be prepared by adjusting the degree of steric hindrance effect according to the type of substituted functional groups. Specifically, the ligands Cp 1 and Cp 2 are respectively substituted by R a and Rb is substituted, wherein R a and R b are the same as or different from each other and each may independently be hydrogen, C 1-20 alkyl, C 2-20 alkoxyalkyl, C 7-40 arylalkyl, or a C 2-12 heteroaryl which is substituted or unsubstituted and contains at least one heteroatom selected from the group consisting of N, O and S, and more specifically is C 1-10 alkyl, C 2-10 alkoxyalkyl, C 7-20 arylalkyl, or a C 4-12 heteroaryl.
[0109] In addition, M 2 Z 2 3-m is present between the ligands Cp 1 and Cp 2 and M 2 Z 2 3-m can affect the storage stability of the metal complex. To effectively ensure this effect, Z 1 can each independently be a halogen or C 1-20 alkyl, more specifically F, Cl, Br or I. In addition, M 2 can each independently be Ti, Zr or Hf; Zr or Hf; or Zr.
[0110] The first metallocene compound can be a compound in which Cp 1 and Cp 2 are each an unsubstituted or substituted cyclopentadienyl, and R a and R b each independently are hydrogen, C 1-10 alkyl, C 2-10 alkoxyalkyl or C 7-20 arylalkyl, wherein at least one of R a and R b is alkoxyalkyl, such as tert-butoxyhexyl, more specifically the substituent -(CH 2 ) p -OR c (wherein R cis a linear or branched alkyl group having 1 to 6 carbon atoms, and p is an integer of 2 to 4). In addition, compared with other Cp-based catalysts that do not contain the above substituents, this case shows a low conversion rate of the comonomer when preparing polyethylene using the comonomer, so low-molecular-weight polyethylene with a controlled copolymerization degree or comonomer distribution can be prepared. In addition, when the first metallocene compound having the above structure is supported on a carrier, the -(CH 2 ) p -OR c group in the substituent can form a covalent bond through a strong interaction with the silanol group on the surface of the silica used as the carrier. Therefore, stable supported polymerization can be carried out.
[0111] The first metallocene compound represented by Chemical Formula 1 may be a compound represented by one of the following structural formulas, but is not limited thereto:
[0112]
[0113] The first metallocene compound represented by Chemical Formula 1 can be synthesized by applying known reactions, and a more specific synthesis method can be understood with reference to the examples.
[0114] Meanwhile, in one embodiment of the present invention, the second metallocene compound represented by Chemical Formula 2 contains an aromatic ring compound containing a cyclopentadienyl or its derivative and a nitrogen atom, and has a structure in which the aromatic ring compound and the nitrogen atom are crosslinked by a bridging group T 2 Q 3 Q 4 Q. The second metallocene compound having this specific structure is suitable for the polymerization reaction of ethylene / 1-hexene copolymer to exhibit high activity and copolymerizability, and can provide a high-molecular-weight olefin copolymer.
[0115] In particular, the second metallocene compound represented by Chemical Formula 2 has a well-known CGC (constrained geometry catalyst) structure. Therefore, the introduction of the comonomer is excellent, and the distribution of the comonomer is controlled by the electronic and steric properties of the ligand. These properties control the ASL (average ethylene sequence length) to increase the medium and high molecular weight regions in the molecular weight distribution, thereby increasing the entanglement fraction of the tie molecules and the entanglement of the polymer chains. Therefore, it is easy to prepare a polyethylene resin that exhibits long-term stability and processability and has excellent mechanical properties.
[0116] M of the metallocene compound represented by Chemical Formula 2 3 may be a Group 4 transition metal, and may preferably be titanium (Ti), zirconium (Zr), or hafnium (Hf).
[0117] Preferably, T in Chemical Formula 2 2 may be silicon.
[0118] Preferably, X in Chemical Formula 2 3 and X 4 may each independently be methyl or chlorine (Cl).
[0119] Preferably, R in Chemical Formula 2 11 to R 14 are the same as or different from each other, and may each independently be methyl or phenyl.
[0120] Preferably, two or more adjacent R 11 to R 14 are connected to each other to form a substituted or unsubstituted aliphatic ring, a substituted or unsubstituted aromatic ring, or a substituted or unsubstituted heteroaromatic ring containing at least one selected from the group consisting of N, O, and S. For example, in Chemical Formula 2, since two or more adjacent R 11 to R 14 are connected to form an aliphatic ring, an aromatic ring, or a heteroaromatic ring, an indenyl, fluorenyl, benzothiophenyl, or dibenzothiophenyl fused with cyclopentadiene can be formed. In addition, the indenyl, fluorenyl, benzothiophenyl, and dibenzothiophenyl may be substituted with one or more substituents.
[0121] Preferably, R in Chemical Formula 2 15 to R 16 may be the same as or different from each other, and may each independently be methyl, ethyl, phenyl, propyl, hexyl, or tert-butoxyhexyl.
[0122] Preferably, R in Chemical Formula 2 17 may be methyl, ethyl, n-propyl, isopropyl, n-butyl, or tert-butyl.
[0123] Since the second metallocene compound can provide a polyethylene resin that is excellent in terms of long-term stability and processability and has excellent mechanical properties due to an increase in the medium- to high-molecular weight region, the metallocene compound of Chemical Formula 2 may be any one selected from the group consisting of the following compounds, but the present invention is not limited thereto:
[0124]
[0125] The second metallocene compound represented by Chemical Formula 2 can be synthesized by applying known reactions. Specifically, it can be prepared by connecting a nitrogen compound with a cyclopentadiene derivative using a bridging compound to prepare a ligand compound, and then adding a metal precursor compound for metallization. However, the method is not limited thereto, and more specific synthesis methods can be understood with reference to the examples and synthesis examples.
[0126] The second metallocene compound represented by Chemical Formula 2 has excellent activity and can polymerize high molecular weight polyethylene resin. In particular, even when used while supported on a carrier, it exhibits high polymerization activity, and thus a polyethylene resin with ultra-high molecular weight can be prepared.
[0127] In addition, even when the polymerization reaction is carried out in the presence of hydrogen to prepare a polyethylene resin with high molecular weight and broad molecular weight distribution, the second metallocene compound represented by Chemical Formula 2 of the present invention also exhibits low hydrogen reactivity, and thus an ultra-high molecular weight polyethylene resin can be copolymerized with high activity. Therefore, even when used in combination with a catalyst having other characteristics, a polyethylene resin satisfying the high molecular weight characteristics can be prepared without deterioration of the activity, and thus a polyethylene resin having a broad molecular weight distribution while containing a high molecular weight polyethylene resin can be easily prepared.
[0128] As described above, in the catalyst composition, the first metallocene compound represented by Chemical Formula 1 can mainly promote the production of a low molecular weight copolymer having a low SCB content, and the second metallocene compound represented by Chemical Formula 2 can mainly promote the production of a high molecular weight copolymer having a high SCB content. More specifically, through the second metallocene compound, the catalyst composition exhibits a high comonomer introduction amount for the comonomer in the high molecular weight region of the copolymer, and through the first metallocene compound, the catalyst composition exhibits a low comonomer introduction amount for the comonomer in the low molecular weight region of the copolymer. As a result, a polyethylene resin having excellent heat resistance and excellent mechanical properties due to a bimodal molecular weight distribution can be prepared.
[0129] In particular, controlling the content ratio of the first and second metallocene compounds in the catalyst composition can achieve the above physical properties and further enhance the improvement effect. Specifically, when the content of the second metallocene compound in the catalyst composition is higher than that of the first metallocene compound, the medium and high molecular weight regions in the molecule increase, so that the tie molecule fraction and the entanglement of the polymer chains increase, thereby optimizing the ratio of the high molecular weight region to the low molecular weight region.
[0130] Specifically, the molar ratio of the first and second metallocene compounds contained should be from 1:1 to 1:8. Preferably, the molar ratio of the first and second metallocene compounds contained can be from 1:1 to 1:7, 1:1 to 1:6, or 1:1 to 1:5.5. When the first and second metallocene compounds are contained within the above range, the balance between the mechanical properties and the elongation rate of the thus-prepared polyethylene resin is controlled. Therefore, it maintains printing suitability, transparency, productivity, and film processability equivalent to or better than conventional materials, and can improve the tensile strength and initial modulus to ensure excellent mechanical properties.
[0131] Meanwhile, the first and second metallocene compounds have the above structural features, so they can be stably supported on the carrier.
[0132] In this case, the first and second metallocene compounds are used in a state supported on the carrier. When used as a supported catalyst, the polymer to be prepared has excellent particle shape and bulk density, and the catalyst can be suitably used for conventional slurry polymerization, bulk polymerization, and gas-phase polymerization.
[0133] The carrier can be silica, alumina, magnesia, or silica-magnesia, and usually can contain oxides, carbonates, sulfates, or nitrates, such as Na 2 O, K 2 CO 3 , BaSO 4 , Mg(NO 3 ) 2 etc. Among the above carriers, the silica carrier hardly releases the catalyst from the surface during the polymerization process because the transition metal compound is supported by chemical bonding with reactive functional groups such as siloxane groups present on the surface of the silica carrier. As a result, when preparing a polymer by slurry polymerization or gas-phase polymerization, fouling phenomena (adhesion to the reactor wall surface or adhesion to each other) can be minimized.
[0134] In addition, in order to increase the loading efficiency and minimize leaching and fouling, the carrier can be surface-modified by calcination or drying. Through the surface-modification step as described above, the moisture on the surface of the carrier that inhibits the reaction with the loading component can be removed, and the content of reactive functional groups (such as hydroxyl groups and siloxane groups) that can chemically bond with the loading component can be increased.
[0135] Specifically, the calcination or drying process of the carrier can be carried out in the temperature range from the temperature at which moisture disappears from the surface of the carrier to the temperature at which reactive functional groups (especially hydroxyl groups (OH groups) present on the surface) are completely eliminated. Specifically, the temperature can be 150°C to 600°C or 200°C to 500°C. When the temperature is low, below 150°C, the moisture removal efficiency is low. As a result, the moisture remaining on the carrier can react with the cocatalyst to reduce the loading efficiency. When the temperature is too high, above 600°C, the pores on the surface of the carrier can combine with each other to reduce the specific surface area, and a large amount of reactive functional groups such as hydroxyl groups or silanol groups may be lost on the surface, leaving only siloxane groups. Therefore, the reaction sites with the cocatalyst may decrease, which is not preferred.
[0136] When the first and second metallocene compounds are supported on a support and the support is silica, based on 1 g of silica, the total loading amount of the first and second metallocene compounds can be 40 μmol or more, or 80 μmol or more, and can be 240 μmol or less, or 160 μmol or less. When loaded within the above range, appropriate loading activity can be exhibited, which is advantageous in terms of maintaining catalyst activity and economic feasibility.
[0137] In addition, in terms of improving high activity and process stability, the catalyst composition may further contain a cocatalyst.
[0138] In the mixed-supported metallocene catalyst of the present invention, the type and content of the cocatalyst further contained are as described above for (a) the first ethylene-α-olefin copolymer, and the specific description is omitted.
[0139] For example, among the above compounds, the cocatalyst can be more specifically an alkylaluminoxane cocatalyst such as methylaluminoxane.
[0140] In addition, the alkylaluminoxane cocatalyst stabilizes the metallocene compound and acts as a Lewis acid. Therefore, by including a metal element capable of forming a bond with the functional group of the bridging group introducing the second metallocene compound through Lewis acid-base interaction, the catalytic activity is further enhanced.
[0141] In addition, the cocatalyst used can be appropriately adjusted according to the desired properties or effects of the catalyst and the resin composition. For example, when silica is used as the support, based on the weight of the support (e.g., 1 g of silica), the loading amount of the cocatalyst can be 8 mmol or more, or 10 mmol or more, and can be 25 mmol or less, or 20 mmol or less.
[0142] In addition, the above catalyst composition can be used as it is for polymerization, or can be used in a prepolymerized state by contacting with an ethylene monomer before the polymerization reaction. In this case, the preparation method according to an embodiment of the present invention may further include a prepolymerization step of contacting the catalyst composition with an ethylene monomer before preparing polyethylene by a polymerization reaction.
[0143] In addition, the catalyst composition can be dissolved or diluted in the following materials and then injected: aliphatic hydrocarbon solvents having 5 to 12 carbon atoms such as pentane, hexane, heptane, nonane, decane and their isomers, aromatic hydrocarbon solvents such as toluene and benzene, or chlorinated hydrocarbon solvents substituted with chlorine such as dichloromethane and chlorobenzene. The solvents used herein are preferably used after treating with a small amount of alkylaluminum to remove a small amount of water or air as a catalyst poison. A cocatalyst can also be further used.
[0144] Meanwhile, the polymerization process can be carried out by contacting ethylene with a comonomer in the presence of the above catalyst composition. In particular, the polymerization reaction can be carried out in a bimodal form using two or more reactors, or in a single polymerization reactor.
[0145] The polymerization can be carried out at a temperature of 25°C to 500°C, preferably 25°C to 200°C, and more preferably 50°C to 150°C. In addition, the polymerization can be carried out at a pressure of 1 kgf / cm 2 to 100 kgf / cm 2 , preferably 1 kgf / cm 2 to 50 kgf / cm 2 and more preferably 5 kgf / cm 2 to 30 kgf / cm 2 .
[0146] In addition, in the copolymerization process, based on the total input weight of ethylene, the input amount of 1-hexene as a comonomer can be about 4.0 wt% to about 6.0 wt%. More specifically, the input amount of 1-hexene can be above about 4.1 wt%, above about 4.2 wt%, above about 4.3 wt%, above about 4.4 wt%, or above about 4.5 wt%, and can be below about 5.9 wt%, below about 5.8 wt%, 5.6 wt% below, below about 5.4 wt%, below about 5.2 wt%, or below about 5.0 wt%.
[0147] Meanwhile, the polyethylene resin of the present invention can be prepared by copolymerizing ethylene and a comonomer in the presence of the above catalyst composition while introducing hydrogen.
[0148] For example, based on the weight of ethylene, the introduction amount of hydrogen can be 35 ppm to 250 ppm, 40 ppm to 200 ppm, 50 ppm to 190 ppm, 55 ppm to 180 ppm, 58 ppm to 170 ppm, or 60 ppm to 145 ppm.
[0149] In the step of loading the catalyst precursor onto the support loaded with the cocatalyst, the supported catalyst can be prepared by adding the first and second transition metal compounds to the support loaded with the cocatalyst, stirring, and then further adding the cocatalyst.
[0150] In the mixed supported metallocene catalyst of the present invention, the amounts of the support, cocatalyst, support loaded with the cocatalyst, and transition metal compound can be appropriately adjusted according to the desired properties or effects of the supported catalyst.
[0151] Meanwhile, when the molar ratio of the first transition metal compound to the second transition metal compound (first transition metal compound: second transition metal compound) is less than 1:0.3, it is difficult to produce very low density polyethylene due to the reduced amount of comonomer introduced. When the ratio exceeds 1:5.5, it is difficult to reproduce the molecular structure of the desired polymer.
[0152] At this time, based on 1 g of the carrier, the loading amount of the metallocene compound supported on the silica carrier can be 0.01 mmol / g to 1 mmol / g. That is, considering the promoting effect of the metallocene compound on the catalyst, it is preferable to control the loading amount within the above range.
[0153] When preparing the mixed supported catalyst, the reaction solvent can be a hydrocarbon solvent such as pentane, hexane, and heptane; or an aromatic solvent such as benzene and toluene.
[0154] For the details of the preparation method of the supported catalyst, refer to the examples described later. However, the preparation method of the supported catalyst is not limited to this specification. The preparation method may also include steps commonly carried out in the technical field of the present invention, and the steps of the preparation method can be changed by steps that can be commonly changed.
[0155] Meanwhile, the above polyethylene copolymer can be prepared by a method including the step of copolymerizing ethylene and an α-olefin in the presence of the above mixed supported metallocene catalyst.
[0156] The above mixed supported catalyst can exhibit excellent loading performance, catalytic activity, and high comonomer introduction amount, and can prepare a polyethylene copolymer capable of producing a polyethylene film having excellent stretchable processing region characteristics and mechanical properties.
[0157] (a) The preparation of the first ethylene-α-olefin copolymer can be carried out by a slurry polymerization method using ethylene and an α-olefin as raw materials with conventional equipment and contacting techniques in the presence of the above mixed supported catalyst.
[0158] (a) The preparation method of the first ethylene-α-olefin copolymer can copolymerize ethylene and an α-olefin using a continuous slurry polymerization reactor, a loop slurry reactor, etc., but the present invention is not limited thereto.
[0159] That is, in the case of the mixed supported metallocene catalyst of the present invention in which the first metallocene compound and the second metallocene compound are loaded within the above molar ratio, due to the interaction of two or more catalysts, the processability, shrinkage, and mechanical properties of the polyethylene copolymer can be further improved.
[0160] In the mixed supported metallocene catalyst of the present invention, the carrier for supporting the first metallocene compound and the second metallocene compound, and further containing a cocatalyst, and the polymerization process are the same as those described above for the (a) first ethylene-α-olefin copolymer, and specific details are omitted.
[0161] As described above, the (a) first ethylene-α-olefin copolymer of the present invention can be prepared by copolymerizing ethylene and an α-olefin using the above supported metallocene catalyst.
[0162] By the above preparation method, the (a) first ethylene-α-olefin copolymer having the above physical properties can be prepared.
[0163] (b) Second ethylene-α-olefin copolymer
[0164] In the polyethylene composition according to an embodiment of the present invention, a (b) second ethylene-α-olefin copolymer having excellent fluidity to have excellent tensile stability and shrinkage resistance is blended with the (a) above-mentioned first ethylene-α-olefin copolymer, thereby adjusting the balance between mechanical properties and elongation. Therefore, it imparts characteristics suitable for manufacturing a polyethylene film, and the polyethylene film has excellent mechanical properties due to having high tensile strength and initial modulus while maintaining printing suitability, transparency, productivity, and film processability equivalent to or superior to conventional materials.
[0165] Specifically, the density of the (b) second ethylene-α-olefin copolymer can be 0.870 g / cm 3 to 0.920 g / cm 3 and the melt index (MI 2.16 , under a load of 190 °C and 2.16 kg) can be 15 g / 10 minutes or less.
[0166] Preferably, the density of the (b) second ethylene-α-olefin copolymer can be 0.880 g / cm 3 or more, 0.890 g / cm 3 or more, 0.895 g / cm 3 or more, or 0.900 g / cm 3 or more, and can be 0.915 g / cm 3 or less, 0.910 g / cm 3 or less, or 0.905 g / cm 3 or less, or 0.904 g / cm 3 or less.
[0167] (b) The melt index (MI 2.16, at 190 °C and a load of 2.16 kg) can be 15 g / 10 min or less, or 13.5 g / 10 min or less, or 12 g / 10 min or less, or 10 g / 10 min or less, or 9.0 g / 10 min or less, or 8.0 g / 10 min or less, or 7.0 g / 10 min or less. In terms of ensuring excellent mechanical properties, high tensile strength and initial modulus during film processing, (b) the melt index (MI of the second ethylene-α-olefin copolymer 2.16 , at 190 °C and a load of 2.16 kg) can be 4.0 g / 10 min or more, or 5.0 g / 10 min or more, or 5.5 g / 10 min or more, or 5.8 g / 10 min or more, or 6.0 g / 10 min or more.
[0168] In addition, (b) the number average molecular weight (Mn) of the second ethylene-α-olefin copolymer can be 20,000 g / mol or more and 50,000 g / mol or less, the weight average molecular weight (Mw) can be 50,000 g / mol or more and 100,000 g / mol or less, and the molecular weight distribution (Mw / Mn) can be 1.5 or more and 4.0 or less.
[0169] Preferably, (b) the number average molecular weight (Mn) of the second ethylene-α-olefin copolymer can be 22,000 g / mol or more, or 23,000 g / mol or more, or 24,000 g / mol or more, or 25,000 g / mol or more, or 28,000 g / mol or more, and can be 45,000 g / mol or less, or 40,000 g / mol or less, or 38,000 g / mol or less, or 35,000 g / mol or less, or 32,000 g / mol or less, or 30,000 g / mol or less.
[0170] (b) The weight average molecular weight (Mw) of the second ethylene-α-olefin copolymer can be 51,000 g / mol or more, or 52,000 g / mol or more, or 55,000 g / mol or more, or 60,000 g / mol or more, or 65,000 g / mol or more, and can be 90,000 g / mol or less, or 85,000 g / mol or less, or 80,000 g / mol or less, or 75,000 g / mol or less, or 70,000 g / mol or less, or 68,000 g / mol or less.
[0171] (b) The molecular weight distribution (Mw / Mn) of the second ethylene-α-olefin copolymer can be 1.7 or more, or 1.9 or more, or 2.0 or more, or 2.1 or more, or 2.2 or more, and can be 3.5 or less, or 3.0 or less, or 2.8 or less, or 2.5 or less, or 2.3 or less.
[0172] Specifically, (b) the second ethylene-α-olefin copolymer may have at least one of the above physical properties and may have all of the above physical properties to exhibit excellent mechanical strength.
[0173] In the present invention, (b) the second ethylene-α-olefin copolymer may contain at least one α-olefin selected from the group consisting of 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, and mixtures thereof, together with ethylene.
[0174] Preferably, (b) the second ethylene-α-olefin copolymer may be an ethylene / 1-octene copolymer.
[0175] When (b) the second ethylene-α-olefin copolymer is the above copolymer, the above physical properties can be easily achieved. However, the type of (b) the second ethylene-α-olefin copolymer is not limited thereto, and various types known in the art may be used as long as they can exhibit the above physical properties.
[0176] Meanwhile, (b) the second ethylene-α-olefin copolymer may be prepared in the presence of a metallocene catalyst.
[0177] Specifically, (b) the second ethylene-α-olefin copolymer may be prepared by copolymerizing ethylene and a comonomer in the presence of a catalyst composition containing a metallocene compound represented by Chemical Formula 3 below:
[0178] [Chemical Formula 3]
[0179]
[0180] In Chemical Formula 3,
[0181] M 1 is a Group 4 transition metal;
[0182] X 1 and X 2 are the same as or different from each other and are each independently a halogen, nitro group, amide group, phosphino group, phosphide group, C1-C30 hydrocarbon group, C1-C30 alkoxy group, C2-C30 alkoxyhydrocarbon group, -SiH 3 , C1-C30 hydrocarbon(oxy)silyl group, C1-C30 sulfonate group, or C1-C30 sulfone group;
[0183] Z is -O-, -S-, -NR a -, or -PR a -;
[0184] R ais any one of hydrogen, a C1-C20 hydrocarbyl group, a C1-C20 hydrocarbyloxy)silyl group, and a C1-C20 silylhydrocarbyl group;
[0185] T is
[0186] T 1 C, Si, Ge, Sn, or Pb,
[0187] Q 1 and Q 2 are the same as or different from each other and are each independently hydrogen, a C1-C30 hydrocarbyl group, a C1-C30 hydrocarbyloxy group, a C2-C30 hydrocarbyloxyhydrocarbyl group, -SiH 3 , a C1-C30 hydrocarbyloxy)silyl group, a halogenated C1-C30 hydrocarbyl group, and -NR b R c any one of;
[0188] R b and R c are each independently at least one of hydrogen and a C1-C30 hydrocarbyl group, or are joined to each other to form an aliphatic ring or an aromatic ring; and
[0189] C 1 is any one of the ligands represented by the following Chemical Formulas 3a to 3d,
[0190] [Chemical Formula 3a]
[0191]
[0192] [Chemical Formula 3b]
[0193]
[0194] [Chemical Formula 3c]
[0195]
[0196] [Chemical Formula 3d]
[0197]
[0198] In Chemical Formulas 3a to 3d,
[0199] Y is O or S, and
[0200] R 1 to R 6 are the same as or different from each other and are each independently any one of hydrogen, a C1-C30 hydrocarbyl group, and a C1-C30 hydrocarbyloxy group.
[0201] Unless otherwise specified herein, the following terms may be defined as follows.
[0202] A hydrocarbyl group is a monovalent functional group in the form of removing one hydrogen from a hydrocarbon, and may include an alkyl group, an alkenyl group, an alkynyl group, an aryl group, an arylalkyl group, an arylalkenyl group, an arylalkynyl group, an alkylaryl group, an alkenylaryl group, an alkynylaryl group, etc. The C1-C30 hydrocarbyl group may be a C1-C20 hydrocarbyl group or a C1-C10 hydrocarbyl group. For example, the hydrocarbyl group may be a straight-chain, branched or cyclic alkyl group. More specifically, the C1-C30 hydrocarbyl group may be, for example, the following straight-chain, branched or cyclic alkyl groups: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl and cyclohexyl; or an aryl group, such as phenyl, biphenyl, naphthyl, anthryl, phenanthryl or fluorenyl. In addition, it may be, for example, the following alkylaryl groups: methylphenyl, ethylphenyl, methylbiphenyl and methylnaphthyl or arylalkyl groups, such as phenylmethyl, phenylethyl, biphenylmethyl and naphthylmethyl. It may also be an alkenyl group, such as allyl, vinyl, propenyl, butenyl and pentenyl.
[0203] A hydrocarbyloxy group is a functional group in which a hydrocarbyl group is bonded to oxygen. Specifically, the C1-C30 hydrocarbyloxy group may be a C1-C20 hydrocarbyloxy group or a C1-C10 hydrocarbyloxy group. For example, the hydrocarbyloxy group may be a straight-chain, branched or cyclic alkyl group. More specifically, the C1-C30 hydrocarbyloxy group may be, for example, the following straight-chain, branched or cyclic alkoxy groups: methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, n-pentyloxy, n-hexyloxy, n-heptyloxy and cyclohexyloxy; or an aryloxy group, such as phenoxy and naphthyloxy.
[0204] A hydrocarbyloxyhydrocarbyl group is a functional group in which at least one hydrogen of a hydrocarbyl group is replaced by at least one hydrocarbyloxy group. Specifically, the C2-C30 hydrocarbyloxyhydrocarbyl group may be a C2-C20 hydrocarbyloxyhydrocarbyl group or a C2-C15 hydrocarbyloxyhydrocarbyl group. For example, the hydrocarbyloxyhydrocarbyl group may be a straight-chain, branched or cyclic alkyl group. More specifically, the C2-C20 hydrocarbyloxyhydrocarbyl group may be, for example, the following straight-chain, branched or cyclic alkoxyalkyl groups: methoxymethyl, methoxyethyl, ethoxymethyl, isopropoxymethyl, isopropoxyethyl, isopropoxyhexyl, tert-butoxymethyl, tert-butoxyethyl and tert-butoxyhexyl; or an aryloxyalkyl group, such as phenoxyhexyl.
[0205] A hydrocarbyl(silyl) group is -SiH 3A functional group in which one to three hydrogens are substituted by one to three hydrocarbyl or hydrocarbyloxy groups. Specifically, a C1-C30 hydrocarbyl(silyl) group can be a C1-C20, C1-C15, C1-C10 or C1-C5 hydrocarbyl(silyl) group. More specifically, a C1-C30 hydrocarbyl(silyl) group can be, for example, an alkylsilyl group such as methylsilyl, dimethylsilyl, trimethylsilyl, dimethylethylsilyl, diethylmethylsilyl or dimethylpropylsilyl; an alkoxysilyl group such as, for example, methoxysilyl, dimethoxysilyl, trimethoxysilyl or dimethoxyethoxysilyl; or an alkoxyalkylsilyl group such as, for example, methoxydimethylsilyl, diethoxymethylsilyl or dimethoxypropylsilyl.
[0206] A C1-C20 silylhydrocarbyl group is a functional group in which at least one hydrogen of a hydrocarbyl group is substituted by a silyl group. The silyl group can be -SiH 3 or a hydrocarbyl(silyl) group. Specifically, a C1-C20 silylhydrocarbyl group can be a C1-C15 silylhydrocarbyl group or a C1-C10 silylhydrocarbyl group. More specifically, a C1-C20 silylhydrocarbyl group can be a silylalkyl group such as -CH 2 -SiH 3 ; an alkylsilylalkyl group such as, for example, methylsilylmethyl, methylsilylethyl, dimethylsilylmethyl, trimethylsilylmethyl, dimethylethylsilylmethyl, diethylmethylsilylmethyl or dimethylpropylsilylmethyl; or an alkoxysilylalkyl group such as, for example, dimethylethoxysilylpropyl.
[0207] The halogen can be fluorine (F), chlorine (Cl), bromine (Br) or iodine (I).
[0208] The sulfonate group can have a structure of -O-SO 2 -R d and R d can be a C1-C30 hydrocarbyl group. Specifically, a C1-C30 sulfonate group can be a methanesulfonate group, a phenylsulfonate group, etc.
[0209] A C1-C30 sulfonyl group has a structure of -R e’ -SO 2 -R e" and R e’ and R e" can be the same as or different from each other and can each independently be any one of C1-C30 hydrocarbyl groups. Specifically, a C1-C30 sulfonyl group can be methylsulfonylmethyl, methylsulfonylpropyl, methylsulfonylbutyl, phenylsulfonylpropyl, etc.
[0210] In the present invention, "two adjacent substituents are connected to each other to form an aliphatic ring or an aromatic ring" means that the atoms of the two substituents and the atoms bonded to the two substituents are connected to each other to form a ring. Specifically, -NR b R c or -NR b’ R c’ The R of b and R c or R b’ and R c’ Examples of being connected to each other to form an aliphatic ring include piperidyl, -NR b R c or -NR b’ R c’ The R of b and R c or R b’ and R c’ Examples of being connected to each other to form an aromatic ring include pyrrolyl.
[0211] The Group 4 transition metal can be titanium (Ti), zirconium (Zr), hafnium (Hf), or (Rf), and can be more specifically titanium (Ti), zirconium (Zr), and hafnium (Hf). More specifically, it can be zirconium (Zr) or hafnium (Hf), but the present invention is not limited thereto.
[0212] In addition, the Group 13 element can be boron (B), aluminum (Al), gallium (Ga), indium (In), or thallium (Tl), and can be specifically boron (B) or aluminum (Al), but the present invention is not limited thereto.
[0213] The above substituents can be optionally substituted with one or more substituents selected from the group consisting of: hydroxyl; halogen; hydrocarbon group; hydrocarbyloxy group; hydrocarbon group or hydrocarbyloxy group containing at least one heteroatom of Group 14 to Group 16 heteroatoms; silyl group; hydrocarbon(oxy)silyl group; phosphino group; phosphide group; sulfonate group; and sulfone group within the range of exhibiting the same or similar effects as the desired effect.
[0214] In the present invention, represents a bond connected to another substituent.
[0215] Specifically, in Chemical Formula 3, Z is -NR a -, wherein R a can be a C1 to C10 hydrocarbon group. Specifically, R a can be a straight-chain or branched C1 to C6 alkyl group. More specifically, it can be a tert-butyl group.
[0216] In Chemical Formula 3, T is wherein T 1 is carbon (C) or silicon (Si), Q1 and Q 2 can each independently be hydrogen, a C1-C30 hydrocarbyl group, or a C1-C30 hydrocarbyloxy group. Specifically, Q 1 and Q 2 can each be a C1-C10 hydrocarbyl group or a C2-C12 hydrocarbyloxyhydrocarbyl group. More specifically, Q 1 and Q 2 can each be a C1-C6 alkyl group, or a C1-C6 alkyl group substituted with a C1-C6 alkoxy group. For example, Q 1 and Q 2 can each independently be hydrogen, methyl, ethyl, or a hexyl group substituted with tert-butyl. More specifically, T 1 is silicon (Si); Q 1 and Q 2 are a hexyl group substituted with methyl or tert-butyl. More specifically, T 1 is silicon (Si); Q 1 and Q 2 is methyl, or one of Q 1 and Q 2 is methyl and the other is a hexyl group substituted with tert-butyl.
[0217] Specifically, the metallocene compound represented by Chemical Formula 3 can be any compound represented by the following Chemical Formulas 3-1 to 3-4.
[0218] [Chemical Formula 3-1]
[0219]
[0220] [Chemical Formula 3-2]
[0221]
[0222] [Chemical Formula 3-3]
[0223]
[0224] [Chemical Formula 3-4]
[0225]
[0226] In Chemical Formulas 3-1 to 3-4, M 1 , X 1 , X 2 , R a , T 1 , Q 1 , Q 2 , Y and R 1 to R 6 are the same as defined in Chemical Formula 3.
[0227] In Chemical Formula 3, R1 to R 4 may each be hydrogen or a C1-C10 hydrocarbon group, and R 5 and R 6 may each be a C1-C10 hydrocarbon group. Specifically, R 1 to R 4 may each be hydrogen or a C1-C10 alkyl group, and R 5 and R 6 may each be a C1-C10 alkyl group. More specifically, R 1 to R 4 may each be hydrogen or methyl, and R 5 and R 6 may be methyl.
[0228] In Chemical Formula 3, M 1 may be titanium (Ti), zirconium (Zr), or hafnium (Hf), and is preferably titanium (Ti).
[0229] In addition, in Chemical Formula 3, X 1 and X 2 may each be a halogen, a C1-C10 alkyl group, or a C1-C6 alkyl group, and are specifically chlorine or methyl.
[0230] In addition, in Chemical Formula 3, the metallocene compound may be represented by one of the following structural formulas.
[0231]
[0232] The metallocene compounds represented by the above structural formulas can be synthesized by applying known reactions, and more specific synthesis methods can be understood with reference to the examples and synthesis examples.
[0233] As described above, the transition metal compound represented by Chemical Formula 3 used in the present invention controls the introduction degree of the α-olefin monomer during the copolymerization process due to the structural characteristics of the catalyst, and exhibits the above density, so the fluidity and stretchability are excellent.
[0234] In the present invention, the polymerization reaction can be carried out by continuously polymerizing ethylene and an α-olefin monomer while continuously introducing hydrogen in the presence of a catalyst composition containing at least one transition metal compound represented by Chemical Formula 3. Specifically, it can be carried out while introducing hydrogen at 5 to 100 cc / min.
[0235] Hydrogen inhibits the rapid reaction of the transition metal compound at the initial stage of polymerization and is used to terminate the polymerization reaction. Therefore, by using hydrogen and adjusting its dosage, an ethylene / α-olefin copolymer with a narrow molecular weight distribution can be effectively produced.
[0236] For example, hydrogen gas can be introduced under the following conditions: above 5 cc / minute, above 7 cc / minute, above 10 cc / minute, above 15 cc / minute, or above 19 cc / minute, and can be below 100 cc / minute, below 50 cc / minute, below 45 cc / minute, below 35 cc / minute, or below 29 cc / minute. When added under the above conditions, the ethylene / α-olefin copolymer to be produced can achieve the physical properties of the present invention.
[0237] When hydrogen gas is introduced at less than 5 cc / minute, the polymerization reaction cannot terminate uniformly, making it difficult to prepare an ethylene / α-olefin copolymer having the desired physical properties. When hydrogen gas is introduced at more than 100 cc / minute, the reaction termination occurs too quickly, so an ethylene / α-olefin copolymer with a very low molecular weight can be produced.
[0238] In addition, the polymerization reaction can be carried out at 100°C to 200°C, and by adjusting the polymerization temperature and the hydrogen input amount, the crystallinity distribution and molecular weight distribution of the ethylene / α-olefin copolymer can be more easily controlled. Specifically, the polymerization reaction can be carried out at 100°C to 200°C, 120°C to 180°C, 130°C to 170°C, or 140°C to 160°C, but is not limited thereto.
[0239] In the present invention, a cocatalyst can be further used in the catalyst composition to activate the transition metal compound of Chemical Formula 3. The cocatalyst is an organometallic compound containing a Group 13 metal, and can specifically include one or more selected from the following Chemical Formulas 4 to 6.
[0240] [Chemical Formula 4]
[0241] R 8 -[Al(R 7 )-O] n -R 9
[0242] In Chemical Formula 4,
[0243] R 7 、R 8 and R 9 are each independently hydrogen, a halogen, a C 1-20 hydrocarbyl group, or a halogenated C 1-20 hydrocarbyl group, and
[0244] n is an integer of 2 or more,
[0245] [Chemical Formula 5]
[0246] D(R 10 ) 3
[0247] In Chemical Formula 5,
[0248] D is aluminum or boron, and
[0249] R 10 is independently selected from halogen, C 1-20 hydrocarbyl, C 1-20 hydroxy, or halogenated C 1-20 hydrocarbyl,
[0250] [Chemical formula 6]
[0251] [L-H] + [W(b) 4 - or [L] + [W(b) 4 -
[0252] In Chemical formula 6,
[0253] L is a neutral or cationic Lewis base,
[0254] H is a hydrogen atom,
[0255] W is a Group 13 element, and
[0256] A is independently selected from any of the following: C 1-20 hydrocarbyl; C 1-20 hydroxy; and substituents in which one or more hydrogen atoms of these substituents are replaced by one or more substituents selected from halogen, C 1-20 hydroxy, and C 1-20 hydrocarbyloxysilyl.
[0257] Specifically, in Chemical formula 6, [L-H] + is a Bronsted acid.
[0258] For example, [L-H] + is trimethylammonium; triethylammonium; tripropylammonium; tributylammonium; diethylammonium; trimethylphosphonium; or triphenylphosphonium, where [L] + is N,N-diethylanilinium; or triphenylcarbenium.
[0259] In addition, in Chemical formula 6, W can be B 3+ or Al 3+ .
[0260] The compound represented by Chemical formula 4 can act as an alkylating agent and an activator, the compound of Chemical formula 5 can act as an alkylating agent, and the compound represented by Chemical formula 6 can act as an activator.
[0261] More specifically, the compound of Chemical Formula 4 can be an alkylaluminoxane compound in which the repeating units are bonded into a linear, cyclic, or network form, and specific examples thereof can include methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane, or tert-butylaluminoxane, etc. Non-limiting examples of the compound represented by Chemical Formula 6 can include methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, tert-butylaluminoxane, etc.
[0262] In addition, non-limiting examples of the compound represented by Chemical Formula 5 can include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum, di-sec-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylmethoxyaluminum, dimethylethoxyaluminum, etc.
[0263] In addition, non-limiting examples of the compound represented by Chemical Formula 6 can include trimethylammonium tetrakis(pentafluorophenyl)borate, triethylammonium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium n-butyltris(pentafluorophenyl)borate, N,N-dimethylanilinium benzyltris(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis(4-(tert-butyldimethylsilyl)-2,3,5,6-tetrafluorophenyl)borate, N,N-dimethylanilinium tetrakis(4-(triisopropylsilyl)-2,3,5,6-tetrafluorophenyl)borate, N,N-dimethylanilinium pentafluorophenoxytri(pentafluorophenyl)borate, N,N-dimethyl-2,4,6-trimethylanilinium tetrakis(pentafluorophenyl)borate, trimethylammonium tetrakis(2,3,4,6-tetrafluorophenyl)borate, N,N-dimethylanilinium tetrakis(2,3,4,6-tetrafluorophenyl)borate, cetyl dimethylammonium tetrakis(pentafluorophenyl)borate, N-methyl-N-dodecylanilinium tetrakis(pentafluorophenyl)borate, methyldi(dodecyl)ammonium tetrakis(pentafluorophenyl)borate, etc.
[0264] Among the above compounds, the cocatalyst can be more specifically an alkylaluminoxane compound such as methylaluminoxane.
[0265] The amount of the cocatalyst can be appropriately adjusted according to the physical properties or effects of the desired mixed supported metallocene catalyst.
[0266] The cocatalyst can be used in an appropriate amount such that the activation of the transition metal compound of Chemical Formula 3 can be fully carried out. The amount of the cocatalyst can be appropriately adjusted according to the physical properties or effects of the desired mixed supported metallocene catalyst or catalyst composition.
[0267] In the present invention, the transition metal compound of Chemical Formula 3 can be used in a state supported on a carrier.
[0268] When the transition metal compound of Chemical Formula 3 is supported on a carrier, the weight ratio of the transition metal compound to the carrier can be from 1:10 to 1:1000, more specifically from 1:10 to 1:500. When the carrier and the transition metal compound are included within the above weight ratio, the best shape can be exhibited. In addition, when a cocatalyst is supported on a carrier, the weight ratio of the cocatalyst to the carrier can be from 1:1 to 1:100, more specifically from 1:1 to 1:50. When the cocatalyst and the carrier are included within the above weight ratio, the activity of the catalyst can be improved and the microstructure of the polymer to be produced can be optimized.
[0269] Meanwhile, the carrier can be silica, alumina, magnesia or a mixture thereof, or can be used in a state containing highly reactive hydroxyl or siloxane groups on its surface by removing moisture from the surface after drying these materials at a high temperature. In addition, the carrier dried at a high temperature usually contains oxides, carbonates, nitrates, such as Na 2 O, K 2 CO 3 , BaSO 4 , Mg(NO 3 ) 2 and so on.
[0270] The drying temperature of the carrier can preferably be about 200 °C to 800 °C, more preferably about 300 °C to 600 °C, and most preferably about 300 °C to 400 °C. When the drying temperature of the carrier is less than 200 °C, due to excessive moisture, the surface moisture can react with the cocatalyst. When the drying temperature of the carrier is greater than 800 °C, the pores on the carrier surface can combine to reduce the surface area, and a large amount of hydroxyl groups on the surface may be lost and only siloxane groups can remain, thus reducing the reaction sites with the cocatalyst, which is not preferred.
[0271] The amount of hydroxyl groups on the carrier surface can preferably be from 0.1 mmol / g to 10 mmol / g, more preferably from 0.5 mmol / g to 5 mmol / g. The amount of hydroxyl groups on the carrier surface can be controlled by the preparation method and preparation conditions or drying conditions (such as temperature, time, vacuum, spray drying, etc.) of the carrier.
[0272] In addition, an organoaluminum compound is further added during the polymerization reaction to remove moisture from the reactor, and the polymerization reaction can be carried out in the presence of the organoaluminum compound. Specific examples of these organoaluminum compounds can include trialkylaluminum, dialkylaluminum halide, alkyldialuminum halide, dialkylaluminum hydride or alkyl sesquialuminum halide. More specific examples thereof can include Al(C 2 H 5 ) 3 , Al(C 2 H5 ) 2 H, Al(C 3 H 7 ) 3 , Al(C 3 H 7 ) 2 H, Al(i-C 4 H 9 ) 2 H, Al(C 8 H 17 ) 3 , Al(C 12 H 25 ) 3 , Al(C 2 H 5 )(C 12 H 25 ) 2 , Al(i-C 4 H 9 )(C 12 H 25 ) 2 , Al(i-C 4 H 9 ) 2 H, Al(i-C 4 H 9 ) 3 , (C 2 H 5 ) 2 AlCl, (i-C 3 H 9 ) 2 AlCl, (C 2 H 5 ) 3 Al 2 Cl 3 etc. These organoaluminum compounds can be continuously added to the reactor, and 0.1 to 10 moles can be added per 1 kg of the reaction medium added to the reactor to sufficiently remove moisture.
[0273] In addition, the polymerization pressure can be about 1 Kgf / cm 2 to about 100 Kgf / cm 2 , preferably about 1 Kgf / cm 2 to about 50 Kgf / cm 2 , and more preferably about 5 Kgf / cm 2 to about 30 Kgf / cm 2 .
[0274] In addition, when the transition metal compound is used in a state supported on a carrier, the transition metal compound can be dissolved or diluted in the following materials and then added: aliphatic hydrocarbon solvents having 5 to 12 carbon atoms such as pentane, hexane, heptane, nonane, decane and their isomers, aromatic hydrocarbon solvents such as toluene and benzene, or chlorinated hydrocarbon solvents substituted with chlorine such as dichloromethane and chlorobenzene. The solvents used herein are preferably used after treating with a small amount of alkylaluminum to remove a small amount of water or air as catalyst poisons. A cocatalyst can also be further used.
[0275] As described above, the (b) second ethylene-α-olefin copolymer can be prepared by copolymerizing ethylene and an α-olefin using the above metallocene catalyst.
[0276] By the above preparation method, the (b) second ethylene-α-olefin copolymer having the above physical properties can be prepared.
[0277] The polyethylene composition of the present invention contains the first ethylene-α-olefin copolymer and the second ethylene-α-olefin copolymer having the optimized density and melt index as described above in appropriate content ratios, respectively, so as to exhibit an increased content of highly crystalline molecules (≥90 °C elution ratio, TREF ≥90℃ ), a lower content of soluble molecules (<35 °C elution ratio, TREF <35℃ ), and a higher antifreeze fraction (35-90 °C elution ratio, TREF <35-90℃ ), a medium crystalline molecule content (35-90 °C elution ratio, TREF <35-90℃ ), and a low soluble fraction (<35 °C elution ratio, TREF <35℃ ), and has a high yield strength and secant modulus (i.e., 1% and 2% initial moduli). Therefore, when the polyethylene composition is applied to film processing, the resulting film exhibits excellent mechanical properties, high tensile strength, and initial modulus while maintaining excellent printability, transparency, productivity, and film processability, thus ensuring excellent mechanical properties and higher film stiffness.
[0278] Polyethylene film
[0279] The polyethylene composition having the above physical properties can stably form a polyethylene film having excellent mechanical properties, high tensile strength, and initial modulus while maintaining excellent printability, transparency, productivity, and film processability.
[0280] At the same time, the polyethylene film can be manufactured by a conventional film manufacturing method, except that the above polyethylene composition is used.
[0281] For example, to manufacture the polyethylene film of the present invention, a laboratory extrusion line (L / D ratio: 42, pitch: 25 mm, melt / T-die temperature: 220 °C) manufactured by Bruckner can be used to prepare a polyethylene composition sheet with a thickness of 0.75 mm. Thereafter, a polyethylene film can be prepared by biaxially stretching a polyethylene composition sheet with dimensions of 90 mm × 90 mm using a KARO 5.0 device. The specific method and conditions are as described in Test Example 3 below.
[0282] For example, the polyethylene film of the present invention can be stably formed into a blown film using the polyethylene composition as described above. Specifically, during the blown film processing, the polyethylene film can be produced from the polyethylene composition by inflation molding using an extruder to achieve a desired thickness, specifically 15 micrometers (μm) to 200 micrometers (μm). Here, the film thickness can be 18 μm to 150 μm, or 20 μm to 100 μm, or 25 μm to 75 μm. Meanwhile, for example, during this film forming process, a single screw extruder (Eugene Engineering Single Screw Extruder, Blown Film M / C, 50Phi, L / D = 32) can be used. Specifically, the extrusion temperature of the extruder can be 120 °C to 200 °C, more specifically 125 °C to 190 °C, or 130 °C to 180 °C. In addition, the blow-up ratio (BUR) can be 3.4 or less, or 0.5 to 3.4, more specifically 2.8 or less, or 1.0 to 2.8, or 2.5 or less, or 1.5 to 2.5. Here, the die gap can be 1 mm to 3 mm, more specifically 1 mm, 1.75 mm, or 3 mm.
[0283] In addition, the polyethylene film of the present invention can contain additives well-known in the art in addition to the above polyethylene copolymer. Specifically, such additives can include solvents, heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, metal deactivators, fillers, reinforcing agents, plasticizers, lubricants, emulsifiers, pigments, optical brighteners, flame retardants, antistatic agents, foaming agents, etc. The type of additives is not particularly limited, and conventional additives known in the art can be used.
[0284] The polyethylene film of one embodiment of the present invention prepared by the above method can have improved properties and excellent stretchable processing area characteristics and mechanical properties.
[0285] Specifically, in a graph where the blow-up ratio (BUR) of 2.2 to 2.5 for the food / industrial film processing field is plotted on the X-axis and the draw speed of 4 m / min to 16 m / min is plotted on the Y-axis, the bubble stability region of the polyethylene film at a blow-up ratio (BUR) of 2.2 to 2.5 and a draw speed of 4 m / min to 16 m / min can account for more than 80%, or more than 90%, or more than 95%, or more than 98%, or 100% of the total area of the graph. Here, the bubble stability can be measured under the condition of 180 °C when the film thickness is 15 μm to 200 μm.
[0286] Specifically, the film formation of the polyethylene composition can be carried out using a single-screw extruder. For example, the film formation of the polyethylene composition can be carried out using a single-screw extruder (Eugene Engineering Single Screw Extruder, Blown Film M / C, 50 Phi, L / D = 32) at an extrusion temperature of 130 °C to 180 °C and a draw speed of 5 m / min to 20 m / min to achieve a thickness of 25 μm to 75 μm through inflation molding. Here, the die gap can be set to 1.0 mm, 1.75 mm, 3.0 mm, and the blow-up ratio can be 2.5. The physical properties of each thickness can be measured from the obtained film according to the die gap and TUR.
[0287] Specifically, the haze of the polyethylene film measured according to the ASTM D 1003 standard under the condition of a film thickness of 25 μm is 28% or less, or 9% to 28%.
[0288] For example, the haze of the film measured by the ASTM D 1003 standard can be 9% (25 μm, die gap 1.0 mm) at 25 μm and a die gap of 1.0 mm, and 28% (25 μm, die gap 3.0 mm) at 25 μm and a die gap of 3.0 mm; or 27% or less, or 15% to 27%; or 26% or less, or 19% to 26%.
[0289] The 45° gloss of the polyethylene film measured according to the ASTM 2457 standard can be 80 GU or more, or 80 GU to 100 GU, preferably 85 GU or more, 88 GU or more, 90 GU or more, or 94 GU or more.
[0290] Meanwhile, the polyethylene film of the present invention exhibits excellent mechanical properties, showing high tensile strength and secant modulus (i.e., 1% and 2% initial modulus).
[0291] Specifically, the tensile strength, 1% tensile modulus, 2% tensile modulus, and elongation at break of the polyethylene film can be measured using a blown film prepared by inflation molding under the following apparatus and conditions. For example, the blown film can be prepared by inflation molding of a polyethylene composition to produce tensile specimens according to the ASTM D 882 standard. Then, for the tensile specimens, tensile tests can be performed in the machine direction (MD) and the transverse direction (TD) according to the ASTM D 882 standard to measure the tensile strength, 1% and 2% initial moduli, and elongation at break. Here, the MD and TD directions of the film can be the longitudinal and transverse directions of the film, respectively.
[0292] - Single screw extruder: Eugene Engineering Single Screw Extruder, Blown Film M / C, 50Phi, L / D = 32
[0293] - Extrusion temperature: 130 °C to 180 °C
[0294] - Die gap: 1 mm to 3 mm
[0295] - Blow-up ratio: 2.5
[0296] - Film thickness: 25 μm to 75 μm
[0297] Specifically, the tensile strength of the polyethylene film in the machine direction (MD) and the transverse direction (TD) measured according to the ASTM D 882 standard can be 40 MPa or more, 42 MPa or more, 44 MPa or more, 46 MPa or more, 48 MPa or more, 49.5 MPa or more, 50 MPa or more, 52 MPa or more, or 54 MPa or more, respectively, and can be 100 MPa or less. For example, the tensile strength of the polyethylene film in the MD direction can be at least 40 MPa, or 42 MPa or more, 44 MPa or more, 46 MPa or more, 48 MPa or more, or 49.5 MPa or more, and the tensile strength in the TD direction can be at least 50 MPa, or 52 MPa or more, or 54 MPa or more.
[0298] Particularly, the MD / TD average tensile strength of the polyethylene film measured according to the ASTM D 882 standard can be 45 MPa or more, 46.5 MPa or more, 48 MPa or more, 49.5 MPa or more, or 50 MPa or more, or 52 MPa or more, and can be 100 MPa or less.
[0299] In addition, as shown by the high initial modulus measured according to ASTM D 882 standard (i.e., the high range of 1% modulus and 2% modulus, which are the initial moduli at 1% and 2% elongation on the stress-strain curves obtained from tensile tests of the film in the machine direction (MD) and transverse direction (TD) measured according to ASTM D 882 standard respectively), the polyethylene film has excellent stiffness. Specifically, the 1% modulus of the polyethylene film in the MD and TD directions can be at least 400 MPa, or above 410 MPa, above 450 MPa, above 480 MPa, above 500 MPa, or above 540 MPa, and can be below 1100 MPa. The 2% modulus of the polyethylene film in the MD and TD directions can be at least 300 MPa, or above 305 MPa, above 330 MPa, above 340 MPa, above 350 MPa, above 375 MPa or above 400 MPa, and below 1000 MPa. For example, the 1% modulus of the polyethylene film in the MD direction can be above 410 MPa, and the 2% modulus of the polyethylene film in the MD direction can be above 305 MPa. In addition, the 1% modulus of the polyethylene film in the TD direction can be above 500 MPa, or above 540 MPa, and the 2% modulus of the polyethylene film in the TD direction can be above 400 MPa, or above 405 MPa. Here, the 1% and 2% modulus values are obtained at the points of 1% and 2% elongation on the stress-strain curves obtained from the tensile tests of the film as described above.
[0300] In particular, the MD / TD average 1% modulus of the polyethylene film measured according to ASTM D 882 standard can be above 450 MPa, or above 460 MPa, above 470 MPa, above 475 MPa, above 480 MPa, above 485 MPa, above 490 MPa, above 500 MPa, above 520 MPa, above 540 MPa, above 550 MPa, above 560 MPa, or above 570 MPa, and can be below 1100 MPa. In addition, the MD / TD average 2% modulus of the polyethylene film measured according to ASTM D 882 standard can be above 350 MPa, or above 355 MPa, above 358 MPa, above 360 MPa, above 365 MPa, above 370 MPa, above 375 MPa, above 390 MPa, above 400 MPa, or above 430 MPa, and can be below 1000 MPa.
[0301] In addition, the elongation at break of the polyethylene film in the machine direction (MD) and the transverse direction (TD) measured according to ASTM D 882 standard can be 630% or more and 998% or less, 650% or more and 997% or less, 680% or more and 995% or less, or 685% or more and 993% or less. For example, the elongation at break of the polyethylene film in the MD can be 630% or more and 750% or less, 650% or more and 745% or less, 680% or more and 740% or less, or 685% or more and 735% or less. The elongation at break of the polyethylene film in the TD can be 750% or more and 998% or less, 765% or more and 997% or less, 780% or more and 995% or less, or 800% or more and 993% or less. Herein, the elongation at break represents the elongation at the break point in the tensile test as described above.
[0302] In particular, the average elongation at break of MD / TD of the polyethylene film measured according to ASTM D 882 standard can be 630% or more and 995% or less, or 735% or more and 815% or less, or 740% or more and 812% or less, or 742% or more and 810% or less, or 743% or more and 800% or less.
[0303] In addition, the tear strength of the polyethylene film in the MD direction measured according to ASTM 1992 standard can be 1.2 N / mm to 4.0 N / mm, or 1.3 N / mm to 3.5 N / mm, or 1.35 N / mm to 3.0 N / mm, or 1.4 N / mm to 2.8 N / mm. The tear strength of the polyethylene film in the TD direction measured according to ASTM 1992 standard can be 8 N / mm to 25 N / mm, or 9 N / mm to 20 N / mm, or 10 N / mm to 18 N / mm, or 10.2 N / mm to 17.9 N / mm.
[0304] In particular, the average tear strength of MD / TD of the polyethylene film measured according to ASTM 1992 standard can be 2 N / mm to 20 N / mm, or 3.5 N / mm to 18 N / mm, or 5 N / mm to 15 N / mm, or 5.5 N / mm to 14 N / mm, or 5.8 N / mm to 13.5 N / mm.
[0305] In the present invention, the physical properties of the polyethylene film can be measured according to the above standards, and the specific method is as described in Test Example 3 below.
[0306] In the present invention, the polyethylene composition contains a first ethylene-α-olefin copolymer having excellent fluidity to impart stretchability and a second ethylene-α-olefin copolymer having excellent mechanical properties in appropriate amounts as described above, thereby adjusting the balance between mechanical properties and elongation. Therefore, it has characteristics suitable for stably forming a polyethylene film, which has excellent mechanical properties and a high initial modulus while maintaining printability, transparency, productivity, and film processability equivalent to or better than those of conventional materials.
[0307] Advantageous Effects
[0308] The polyethylene of the present invention has an excellent effect of producing a polyethylene film, which has excellent mechanical properties and a high initial modulus while maintaining excellent printability, transparency, productivity, and film processability. Detailed Description of the Invention
[0309] Hereinafter, embodiments of the present invention will be described in more detail in the following examples. However, the following examples are for illustrative purposes only and are not intended to limit the present invention.
[0310] Examples
[0311] <Preparation of Metallocene Compound>
[0312] Synthesis Example 1
[0313]
[0314] t-Bu-O-(CH 2 ) 6 -Cl was prepared using 6-chlorohexanol by the method shown in Tetrahedron Lett. 2951 (1988), and reacted with Na(C 5 H 5 )[NaCp] to obtain t-Bu-O-(CH 2 ) 6 -C 5 H 5 (yield 60%, boiling point 80 °C / 0.1 mmHg).
[0315] Furthermore, t-Bu-O-(CH 2 ) 6 -C 5 H 5 was dissolved in tetrahydrofuran (THF) at -78 °C, and n-BuLi was slowly added thereto. Thereafter, it was heated to room temperature and reacted for 8 hours. The lithium salt solution synthesized as above was slowly added to ZrCl 4 (THF) 2in a suspension solution (170 g, 4.50 mmol) / THF (30 mL), and the reaction was further carried out at room temperature for about 6 hours. All volatiles were dried under vacuum and the resulting oily liquid material was filtered by adding hexane solvent. The filtered solution was dried under vacuum, and hexane was added at low temperature (-20 °C) to obtain a precipitate. The resulting precipitate was filtered at low temperature to obtain the [t-Bu-O-(CH 2 ) 6 -C 5 H 4 2 ZrCl 2 compound (yield 92%).
[0316] 1 1H-NMR (300 MHz, CDCl 3 3): δ 6.28 (t, J = 2.6 Hz, 2H), 6.19 (t, J = 2.6 Hz, 2H), 3.31 (t, 6.6 Hz, 2H), 2.62 (t, J = 8 Hz), 1.7 - 1.3 (m, 8H), 1.17 (s, 9H).
[0317] 13 13C-NMR (CDCl 3 3): δ 135.09, 116.66, 112.28, 72.42, 61.52, 30.66, 30.31, 30.14, 29.18, 27.58, 26.00.
[0318] Synthesis Example 2
[0319]
[0320] At room temperature, 50 g of Mg (solid) was added to a 10 L reactor, and then 300 mL of THF was added. 0.5 g of I 2 was added and the reactor temperature was maintained at 50 °C. After the reactor temperature was stabilized, 250 g of 6-tert-butoxyhexyl chloride was added to the reactor at a flow rate of 5 mL / minute using a feed pump. It was observed that the reactor temperature rose by 4 to 5 °C with the addition of 6-tert-butoxyhexyl chloride. Stirring was carried out for 12 hours while continuously adding 6-tert-butoxyhexyl chloride. After 12 hours of reaction, a black reaction solution was obtained. 2 mL of the black solution was taken, and water was added thereto to obtain an organic layer. By 1 1H-NMR, it was confirmed that the organic layer was 6-tert-butoxyhexane. Thus, it was confirmed that the Grignard reaction proceeded sufficiently. Therefore, 6-tert-butoxyhexylmagnesium chloride was synthesized.
[0321] 500 g of MeSiCl 3 1 L of THF was added to the reactor, and then the reactor temperature was cooled to -20 °C. 560 g of the above-synthesized 6-tert-butoxyhexylmagnesium chloride was added to the reactor at a flow rate of 5 mL / min using a feed pump. After the supply of the Grignard reagent was completed, the mixture was stirred for 12 hours while slowly raising the reactor temperature to room temperature. After 12 hours of reaction, it was confirmed that MgCl 2 salt was produced. 4 L of hexane was added thereto and the salt was removed by labdori to obtain a filtered solution. After adding the filtered solution to the reactor, hexane was removed at 70 °C to obtain a pale yellow liquid. By 1 1H-NMR, it was confirmed that the obtained liquid was methyl(6-tert-butoxyhexyl)dichlorosilane.
[0322] 1 1H-NMR (300 MHz, CDCl 3 3): δ 3.3 (t, 2H), 1.5 (m, 3H), 1.3 (m, 5H), 1.2 (s, 9H), 1.1 (m, 2H), 0.7 (s, 3H).
[0323] 1.2 mol (150 g) of tetramethylcyclopentadiene and 2.4 L of THF were added to the reactor, and then the reactor temperature was cooled to -20 °C. 480 mL of n-BuLi was added to the reactor at a flow rate of 5 mL / min using a feed pump. After adding n-BuLi, the mixture was stirred for 12 hours while slowly raising the reactor temperature to room temperature. After 12 hours of reaction, 1 equivalent of methyl(6-tert-butoxyhexyl)dichlorosilane (326 g, 350 mL) was rapidly added to the reactor. The mixture was stirred for 12 hours while slowly raising the reactor temperature to room temperature. Then, the reactor temperature was cooled to 0 °C again, and 2 equivalents of t-BuNH 2 2 was added. The mixture was stirred for 12 hours while slowly raising the reactor temperature to room temperature. After 12 hours of reaction, THF was removed. Thereafter, 4 L of hexane was added and the salt was removed by labdori to obtain a filtered solution. The filtered solution was added to the reactor again, and hexane was removed at 70 °C to obtain a yellow solution. By 1 1H-NMR, it was confirmed that the above-obtained yellow solution was methyl(6-tert-butoxyhexyl)(tetramethylCpH)tert-butylaminosilane.
[0324] TiCl 3 (THF) 3(10 mmol) was rapidly added to the dilithium salt of the ligand synthesized from n-BuLi and dimethyl(tetramethyl Cp)tert-butylaminosilane ligand in a THF solution. The reaction solution was stirred for 12 hours while being slowly heated from -78 °C to room temperature. After stirring for 12 hours, 1 equivalent of PbCl 2 (10 mmol) was added to the reaction solution, and then it was stirred for 12 hours. After stirring for 12 hours, a dark black solution with a slightly blue color was obtained. THF was removed from the resulting reaction solution, and then hexane was added to filter the product. Hexane was removed from the filtered solution, and then the product was confirmed by 1 1H-NMR to be (tBu-O-(CH 2 ))(CH 6 )(CH 3 )Si(C 5 (CH 3 ))(tBu-N)TiCl 4 ([Methyl(6-tert-butoxyhexyl)silyl(η5-tetramethyl Cp)(tert-butylamido)]TiCl 2 ). 2 )
[0325] 1 1H-NMR (300 MHz, CDCl 3 ): δ 3.3 (s, 4H), 2.2 (s, 6H), 2.1 (s, 6H), 1.8 - 0.8 (m), 1.4 (s, 9H), 1.2 (s, 9H), 0.7 (s, 3H).
[0326] Synthesis Example 3
[0327] (1) Preparation of ligand A
[0328] 4.0 g (30 mmol) of 1-benzothiophene was dissolved in THF to prepare a 1-benzothiophene solution. Then, 14 mL (36 mmol, 2.5 M hexane solution) of n-BuLi solution and 1.3 g (15 mmol) of CuCN were added to the 1-benzothiophene solution. Then, 3.6 g (30 mmol) of crotonyl chloride was slowly added to the above solution at -80 °C, and the resulting solution was stirred at room temperature for about 10 hours. Thereafter, 10% HCl was poured into the above solution to quench the reaction, and the organic layer was separated with dichloromethane to obtain (2E)-1-(1-benzothiophen-2-yl)-2-methyl-2-buten-1-one in the form of a beige solid.
[0329]
[0330] 1 1H NMR (CDCl3 ):δ 7.85 - 7.82 (m, 2H), 7.75 (m, 1H), 7.44 - 7.34 (m, 2H), 6.68 (m, 1H), 1.99 (m, 3H), 1.92 (m, 3H).
[0331] 34 mL of sulfuric acid was slowly added to a solution obtained by dissolving 5.0 g (22 mmol) of the above-prepared (2E)-1-(1-benzothiophen-2-yl)-2-methyl-2-buten-1-one in 5 mL of chlorobenzene while stirring vigorously. Then, the solution was stirred at room temperature for about 1 hour. Thereafter, ice water was poured into the solution, and the organic layer was separated with an ether solvent, and 4.5 g of 1,2-dimethyl-1,2-dihydro-3H-benzo[b]cyclopenta[d]thiophen-3-one in the form of a yellow solid was obtained (91% yield).
[0332]
[0333] 1 H NMR(CDCl 3 ):δ 7.95 - 7.91 (m, 2H), 7.51 - 7.45 (m, 2H), 3.20 (m, 1H), 2.63 (m, 1H), 1.59 (d, 3H), 1.39 (d, 3H).
[0334] At 0 °C, 570 mg (15 mmol) of NaBH 4 was added to a solution obtained by dissolving 2.0 g (9.2 mmol) of 1,2-dimethyl-1,2-dihydro-3H-benzo[b]cyclopenta[d]thiophen-3-one in a mixed solvent of 20 mL of THF and 10 mL of methanol. Then, the solution was stirred at room temperature for about 2 hours. In addition, HCl was added to the solution to adjust the pH to 1, and the organic layer was separated with an ether solvent to obtain an alcohol intermediate.
[0335] The alcohol intermediate was dissolved in toluene to prepare a solution. Then, 190 mg (1.0 mmol) of p-toluenesulfonic acid was added to the solution, and the mixture was refluxed for about 10 minutes. The resulting reaction mixture was separated by column chromatography to obtain 1.8 g (9.0 mmol, 98% yield) of 1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophene (ligand A) in the form of an orange-brown liquid.
[0336]
[0337] 1 H NMR(CDCl 3):δ 7.81 (d, 1H), 7.70 (d, 1H), 7.33 (t, 1H), 7.19 (t, 1H), 6.46 (s, 1H), 3.35 (q, 1H), 2.14 (s, 3H), 1.14 (d, 3H).
[0338] (2) Preparation of ligand B
[0339] 13 mL (120 mmol) of tert - butylamine and 20 mL of an ether solvent were added to a 250 mL Schlenk flask, and 16 g (60 mmol) of (6 - tert - butoxyhexyl)dichloro(methyl)silane and 40 mL of an ether solvent were added to another 250 mL Schlenk flask to prepare a tert - butylamine solution and a (6 - tert - butoxyhexyl)dichloro(methyl)silane solution, respectively. Then, the tert - butylamine solution was cooled to - 78 °C, and the (6 - tert - butoxyhexyl)dichloro(methyl)silane solution was slowly injected into the cooled solution, followed by stirring at room temperature for about 2 hours. The resulting white suspension was filtered to obtain 1 - (6 - (tert - butoxy)hexyl)-N - (tert - butyl)-1 - chloro - 1 - methylsilane (ligand B) in the form of an ivory - colored liquid.
[0340]
[0341] 1 H NMR(CDCl 3 ):δ 3.29 (t, 2H), 1.52 - 1.29 (m, 10H), 1.20 (s, 9H), 1.16 (s, 9H), 0.40 (s, 3H).
[0342] (3) Cross - linking of ligands A and B
[0343] 1.7 g (8.6 mmol) of 1,2 - dimethyl - 3H - benzo[b]cyclopenta[d]thiophene (ligand A) was added to a 250 mL Schlenk flask, and then 30 mL of THF was added to prepare a ligand A solution. After cooling the ligand A solution to - 78 °C, 3.6 mL (9.1 mmol, 2.5 M hexane solution) of n - BuLi solution was added to the ligand A solution. Then, the mixture was stirred overnight at room temperature to prepare a purple - brown solution. The solvent of the purple - brown solution was replaced with toluene, and a solution obtained by dispersing 39 mg (0.43 mmol) of CuCN in 2 mL of THF was injected into it to prepare solution A.
[0344] Meanwhile, 1-(6-(tert-Butoxy)hexyl)-N-(tert-butyl)-1-chloro-1-methylsilane (Ligand B) and toluene were injected into a 250 mL Schlenk flask to prepare Solution B, which was cooled to -78 °C. The above-prepared Solution A was slowly injected into the cooled Solution B. Then, the mixture of Solutions A and B was stirred overnight at room temperature. Thereafter, the resulting solid was removed by filtration to obtain 4.2 g (>99% yield) of a brown viscous liquid, 1-(6-(tert-butoxy)hexyl)-N-(tert-butyl)-1-(1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophen-3-yl)-1-methylsilane (the cross-linked product of Ligands A and B).
[0345]
[0346] To confirm the structure of the cross-linked product of Ligands A and B, the cross-linked product was lithiated at room temperature and then an H-NMR spectrum was obtained using a sample dissolved in a small amount of pyridine-D5 and CDCl 3 .
[0347] 1 H NMR (pyridine-D5 and CDCl 3 ): δ 7.81 (d, 1H), 7.67 (d, 1H), 7.82 - 7.08 (m, 2H), 3.59 (t, 2H), 3.15 (s, 6H), 2.23 - 1.73 (m, 10H), 2.15 (s, 9H), 1.91 (s, 9H), 1.68 (s, 3H).
[0348] (4) Preparation of transition metal compound
[0349] 4.2 g (8.6 mmol) of 1-(6-(tert-butoxy)hexyl)-N-(tert-butyl)-1-(1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophen-3-yl)-1-methylsilane (the cross-linked product of Ligands A and B) was added to a 250 mL Schlenk flask, and 14 mL of toluene and 1.7 mL of n-hexane were added to the flask to dissolve the cross-linked product. The solution was cooled to -78 °C, and then 7.3 mL (18 mmol, 2.5 M hexane solution) of n-BuLi solution was injected into the cooled solution. Thereafter, the solution was stirred at room temperature for about 12 hours. Then, 5.3 mL (38 mmol) of trimethylamine was added to the solution, followed by stirring at about 40 °C for about 3 hours to prepare Solution C.
[0350] Meanwhile, 2.3 g (8.6 mmol) of TiCl 4 (THF) 210 mL of toluene was added to a separately prepared 250 mL Schlenk flask to prepare a solution of TiCl 4 (THF) 2 Solution D dispersed in toluene. At -78 °C, solution C prepared before solution D was slowly injected, and the mixture of solution C and D was stirred at room temperature for about 12 hours. Thereafter, the solution was depressurized to remove the solvent, and the resulting solute was dissolved in toluene. Then, the solid that did not dissolve in toluene was removed by filtration, and the solvent was removed from the filtered solution to obtain 4.2 g (83% yield) of a transition metal compound in the form of a brown solid.
[0351]
[0352] 1 H NMR (CDCl 3 ): δ 8.01 (d, 1H), 7.73 (d, 1H), 7.45 - 7.40 (m, 2H), 3.33 (t, 2H), 2.71 (s, 3H), 2.33 (d, 3H), 1.38 (s, 9H), 1.18 (s, 9H), 1.80 - 0.79 (m, 10H), 0.79 (d, 3H).
[0353] Synthesis Example 4
[0354]
[0355] (1) Preparation of ligand compound: Synthesis of N-tert-butyl-1-(1,2-dimethyl-3H-benzo[b]cyclopenta[d]thiophen- 3-yl)-1,1-dimethylsilane
[0356] 4.65 g (15.88 mmol) of the compound of Formula 1 was added to a 100 mL Schlenk flask, and then 80 mL of THF was added thereto. After adding tBuNH 2 (4 equivalents, 6.68 mL) at room temperature, the mixture was reacted at room temperature for 3 days. After the reaction, THF was removed, and the mixture was filtered with hexane. After drying the solvent, 4.50 g (yield: 86%) of a yellow liquid was obtained.
[0357] 1 H-NMR (500 MHz, CDCl 3 ): δ 7.99 (d, 1H), 7.83 (d, 1H), 7.35 (dd, 1H), 7.24 (dd, 1H), 3.49 (s, 1H), 2.37 (s, 3H), 2.17 (s, 3H), 1.27 (s, 9H), 0.19 (s, 3H), -0.17 (s, 3H).
[0358] (2) Preparation of transition metal compound
[0359] The ligand compound (1.06 g, 3.22 mmol / 1.0 eq) and 16.0 mL of MTBE (0.2 M) were added to a 50 mL Schlenk flask and stirred first. At -40 °C, n-BuLi (2.64 mL, 6.60 mmol / 2.05 eq, 2.5 M THF solution) was added and the reaction was carried out overnight at room temperature. Thereafter, MeMgBr (2.68 mL, 8.05 mmol / 2.5 eq, 3.0 M ether solution) was slowly added dropwise at -40 °C, and then TiCl 4 (2.68 mL, 3.22 mmol / 1.0 eq, 1.0 M toluene solution) was added thereto, and the reaction was carried out overnight. Then, filtration was performed through diatomaceous earth using hexane. After drying the solvent, 1.07 g (yield: 82%) of a brown solid was obtained.
[0360] 1 1H-NMR (500 MHz, CDCl 3 3): δ 7.99 (d, 1H), 7.68 (d, 1H), 7.40 (dd, 1H), 7.30 (dd, 1H), 3.22 (s, 1H), 2.67 (s, 3H), 2.05 (s, 3H), 1.54 (s, 9H), 0.58 (s, 3H), 0.57 (s, 3H), 0.40 (s, 3H), -0.45 (s, 3H).
[0361] <Preparation of Supported Catalyst>
[0362] Preparation Example 1: Preparation of Supported Metallocene Catalyst 1
[0363] 5.0 kg of a toluene solution was added to a 20 L stainless steel (sus) high-pressure reactor, and the reactor temperature was maintained at 40 °C. 1000 g of silica (manufactured by Grace Davison, SYLOPOL 948) dehydrated by applying a vacuum at 600 °C for 12 hours was added to the reactor and dispersed well, and then 80 g of the first metallocene compound of Synthesis Example 1 was dissolved in the toluene solution and added thereto, and then the reaction was carried out with stirring at 200 rpm for 2 hours at 40 °C. Thereafter, stirring was stopped, left standing for 30 minutes, and the reaction solution was decanted.
[0364] 2.5 kg of toluene was added to the reactor, and 9.4 kg of a 10 wt% methylaluminoxane (MAO) / toluene solution was added thereto, and then the reaction was carried out with stirring at 200 rpm for 12 hours at 40 °C. After the reaction, it was left standing for 30 minutes, and the reaction solution was decanted. After adding 3.0 kg of toluene and stirring for 10 minutes, stirring was stopped, left standing for 30 minutes, and the toluene solution was decanted.
[0365] 3.0 kg of toluene was added to the reactor, and then 314 mL of a 29.2 wt% solution of the second metallocene compound in toluene from Synthesis Example 2 was added to the reactor. Subsequently, the mixture was stirred at 40 °C at 200 rpm for 2 hours to carry out the reaction. At this time, the molar ratio of the first metallocene compound to the second metallocene compound was 1:5. After the temperature of the reactor was lowered to room temperature, stirring was stopped, and the mixture was allowed to stand for 30 minutes, and then the reaction solution was decanted.
[0366] After adding 2.0 kg of toluene and stirring for 10 minutes, stirring was stopped, and the mixture was allowed to stand for 30 minutes, and then the reaction solution was decanted.
[0367] 3.0 kg of hexane was added to the reactor, and the hexane slurry was transferred to a filter dryer and the hexane solution was filtered. It was dried under reduced pressure at 40 °C for 4 hours to prepare 910 g of SiO 2 Mixed supported catalyst.
[0368] Preparation Example 2: Preparation of Mixed Supported Metallocene Catalyst 2
[0369] 3.0 kg of toluene solution was added to a 20 L stainless steel (SUS) autoclave, and the temperature of the reactor was maintained at 40 °C. 500 g of silica (manufactured by Grace Davison, SP2212) dehydrated by applying a vacuum at 600 °C for 12 hours was added to the reactor and thoroughly dispersed. Then, 2.78 kg of a 10 wt% methylaluminoxane (MAO) / toluene solution was added thereto, and subsequently, the mixture was stirred at 80 °C at 200 rpm for 15 hours to carry out the reaction.
[0370] After the temperature of the reactor was lowered to 40 °C, 200 g of the first metallocene compound / toluene solution (7.8 wt% toluene solution) prepared in Synthesis Example 1 was added to the reactor and stirred at 200 rpm for 1 hour. Subsequently, 250 g of the second metallocene compound / toluene solution (7.8 wt% toluene solution) prepared in Synthesis Example 3 was added to the reactor and stirred at 200 rpm for 1 hour (molar ratio of the first metallocene compound: second metallocene compound = 1:1.3).
[0371] 70 g of a cocatalyst (anilinium tetrakis(pentafluorophenyl)borate) was diluted in toluene and then added to the reactor, and subsequently, the mixture was stirred at 200 rpm for more than 15 hours. After the temperature of the reactor was lowered to room temperature, stirring was stopped, and the mixture was allowed to stand for 30 minutes, and then the reaction solution was decanted.
[0372] Transfer the toluene slurry to a filter dryer and filter it. After adding 3.0 kg of toluene and stirring for 10 minutes, stop stirring and filter. Add 3.0 kg of hexane to the reactor and stir for 10 minutes, then stop stirring and filter. Dry it under reduced pressure at 50 °C for 4 hours to prepare 500 g of SiO 2 Supported catalyst.
[0373] <Preparation of Ethylene-α-Olefin Copolymer>
[0374] Preparation Example 3: Preparation of ethylene / 1-hexene copolymer (PE-a)
[0375] In the presence of the supported mixed catalyst prepared in Preparation Example 1, slurry polymerization of ethylene / 1-hexene copolymer (PE-a) was carried out.
[0376] At this time, the polymerization reactor was an isobutane (i-C4) slurry loop process, a continuous polymerization reactor, and the reactor volume was 140 L, and the flow rate was about 7 m / sec. The gases (ethylene, hydrogen) and comonomer 1-hexene required for polymerization were introduced constantly and continuously, and the flow rates were adjusted according to the target product. At this time, the ethylene input amount was 31.1 kg / hour, the 1-hexene input amount was adjusted to 2.5 wt% compared with ethylene, and the hydrogen input amount was adjusted to 56 ppm compared with ethylene. In addition, the concentrations of all gases and 1-hexene comonomer in Preparation Example 1 were confirmed by an on-line gas chromatograph. The supported catalyst was prepared and introduced as an isobutane slurry with a concentration of 4 wt%, the reactor pressure was maintained at about 40 bar, and the polymerization temperature was about 80 °C.
[0377] Preparation Example 4: Preparation of ethylene / 1-hexene copolymer (PE-b)
[0378] Ethylene / 1-hexene copolymer was prepared by a single-peak polymerization process.
[0379] Specifically, under the conditions of an ethylene input of 10.0 kg / hour, an input of 1-hexene as a comonomer of 6.3 ml / minute, and an input of hydrogen of 1.73 g / hour, in a loop reactor (polymerization temperature: 93 °C, polymerization pressure: 7.7 kgf / cm 2 ) and a hexane slurry stirred tank process polymerization reactor, ethylene / 1-hexene copolymer (PE-b) was obtained using the mixed supported metallocene catalyst 2 prepared in Preparation Example 2.
[0380] The catalyst activity was obtained by measuring the weight of the catalyst used in the polymerization reactor and the weight of the polymer prepared by the polymerization reaction, and then calculating the weight ratio of the prepared polymer to the weight of the catalyst used, and was confirmed to be 9.9 kg PE / g catalyst·hour.
[0381] Preparation Example 5: Preparation of ethylene / 1-octene copolymer (PE-c)
[0382] While adding 5 kg / h of hexane solvent and 0.31 kg / h of 1-octene, a 1.5 L continuous process reactor was preheated at 120 °C. Triisobutylaluminum (Tibal, 0.045 mmol / min), the transition metal compound obtained in Synthesis Example 3, and a dimethylanilinium tetrakis(pentafluorophenyl)borate cocatalyst (2.6 μmol / min) were simultaneously added to the reactor. Subsequently, in a continuous process at a pressure of 89 bar, ethylene (0.87 kg / h) and hydrogen (10 cc / min) were introduced into the reactor and maintained at 160.0 °C for more than 60 minutes to carry out a copolymerization reaction to obtain an ethylene / 1-octene copolymer (PE-c).
[0383] Preparation Example 6: Preparation of ethylene / 1-hexene copolymer (PE-d)
[0384] As the ethylene / 1-hexene copolymer, a commercially available product (LG Chem Ltd. SE0327N, metallocene catalyst, density: 0.931 g / cm 3 , MI 2.16 : 0.3 g / 10 min) was used.
[0385] Preparation Example 7: Preparation of ethylene / 1-octene copolymer (PE-e)
[0386] While adding 0.28 kg / h of hexane solvent and 0.31 kg / h of 1-octene, a 1.5 L continuous process reactor was preheated at 120 °C. Triisobutylaluminum (Tibal, 0.045 mmol / min), the transition metal compound obtained in Synthesis Example 3, and a dimethylanilinium tetrakis(pentafluorophenyl)borate cocatalyst (2.6 μmol / min) were simultaneously added to the reactor. Subsequently, in a continuous process at a pressure of 89 bar, ethylene (0.87 kg / h) and hydrogen (18 cc / min) were introduced into the reactor and maintained at 160.0 °C for more than 60 minutes to carry out a copolymerization reaction to obtain an ethylene / 1-octene copolymer (PE-e).
[0387] <Test Example 1: Evaluation of Physical Properties of Polyethylene>
[0388] The physical properties of the ethylene-α-olefin copolymers prepared in Preparation Examples 3 to 7 were measured by the following method and are shown in Table 1.
[0389] (1) Density
[0390] The density (g / cm 3 ) was measured using a density gradient column according to ASTM D 1505 (American Society for Testing and Materials).
[0391] (2) Melt Index
[0392] The melt index (MI 2.16 ) was measured at 190 °C under a load of 2.16 kg in accordance with ASTM D 1238 (Condition E, 190 °C, 2.16 kg) of the American Society for Testing and Materials and is expressed as the weight (g) of the polymer melted within 10 minutes. 2.16 (Measuring equipment: MI-4 manufactured by Gottfert)
[0393] (3) Number-average molecular weight (Mn), weight-average molecular weight (Mw), and molecular weight distribution (Mw / Mn)
[0394] Regarding the ethylene-α-olefin copolymers prepared in Preparation Examples 3 to 7, the molecular weight distribution (Mw / Mn, PDI, polydispersity index) was calculated as follows: The weight-average molecular weight (Mw, g / mol) and number-average molecular weight (Mn, g / mol) were measured using a gel permeation chromatograph (GPC, manufactured by Waters) in accordance with ASTM D 6474 (American Society for Testing and Materials), and then the weight-average molecular weight was divided by the number-average molecular weight.
[0395] Specifically, PL-GPC220 manufactured by Waters was used as the gel permeation chromatography (GPC) instrument, and a Polymer Laboratories PLgel MIX-B 300 mm long column was used. The evaluation temperature was 160 °C, and 1,2,4-trichlorobenzene was used as the solvent at a flow rate of 1 mL / minute. Each ethylene-α-olefin copolymer prepared in Preparation Examples 3 to 7 was pretreated by dissolving it in 1,2,4-trichlorobenzene containing 0.0125% of BHT at 160 °C for 3 hours, and a sample with a concentration of 32 mg / 10 mL was supplied in an amount of 200 μL. The Mw and Mn values were obtained using a calibration curve formed with polystyrene standards. Nine polystyrene standards with molecular weights of 2000 g / mol, 10000 g / mol, 30000 g / mol, 70000 g / mol, 200000 g / mol, 700000 g / mol, 2000000 g / mol, 4000000 g / mol, and 10000000 g / mol were used.
[0396] [Table 1]
[0397]
[0398] [Preparation of Polyethylene Composition]
[0399] Examples 1 to 5 and Comparative Examples 1 to 3
[0400] The polyethylene compositions of Examples 1 to 5 and Comparative Examples 1 to 3 were prepared using the above ethylene-α-olefin copolymers of Preparation Examples 3 to 7 with the compositions shown in Tables 2 and 3 below, respectively.
[0401] Specifically, a polyethylene composition was prepared by extrusion and granulation at 220 °C using a twin extruder (extruder: TEK30MHS from SMPLATEK, L / D ratio: 40, die diameter: 4 mm) with a hopper at 18 rpm and a screw at 350 rpm.
[0402] Comparative Example 4
[0403] The polyethylene composition of Comparative Example 4 was prepared in the same manner as in Example 1, except that a commercially available ethylene / 1-hexene copolymer polyethylene product HP1018 TM (manufactured by LG Chem, Ltd.) was used as a single component (PE-f, 100%).
[0404] Here, the density of the ethylene / 1-hexene copolymer (PE-f) was 0.918 g / cm 3 and the melt index (MI 2.16 , at a load of 190 °C and 2.16 kg) was 1.0 g / 10 min.
[0405] <Test Example 2: Evaluation of Physical Properties of Polyethylene Composition>
[0406] The physical properties of the polyethylene compositions prepared in the examples and comparative examples were measured by the following methods and are shown in Tables 2 and 3, respectively.
[0407] First, the melt index (MI 2.16 )、density, weight average molecular weight (Mw, g / mol), number average molecular weight (Mn, g / mol), and molecular weight distribution (Mw / Mn, PDI) of the polyethylene composition were measured in the same manner as in Test 1 above.
[0408] (4) Melting temperature, crystallization temperature, and crystallinity
[0409] The melting temperature (Tm), crystallization temperature (Tc), and crystallinity (Xc) of the polyethylene compositions of the examples and comparative examples were measured using a differential scanning calorimeter (DSC, equipment name: DSC Q20, manufacturer: TA instrument).
[0410] Specifically, the polyethylene composition was heated to 180 °C at 10 °C / min (cycle 1), isothermally held at 180 °C for 5 minutes, cooled to 0 °C at 10 °C / min, isothermally held at 30 °C for 5 minutes, and then heated to 180 °C again at 10 °C / min (cycle 2). In the DSC curve obtained above, the temperature at the maximum point of the endothermic peak was measured as the melting point (Tm, °C), and the temperature at the maximum point of the exothermic peak was measured as the crystallization temperature (Tc, °C). At this time, the melting point (Tm) and the crystallization temperature (Tc) are shown as the measurement results in cycle 2 of the second heating and cooling.
[0411] In addition, the heat of fusion ΔHm was obtained by calculating the area of the melting peak in cycle 2 of the second heating and cooling, and the crystallinity (Xc) was calculated by dividing ΔHm by H 0 m = 293.6 J / g (theoretical value when the crystallinity is 100%).
[0412] (5) Cross Fractionation Chromatography (CFC)
[0413] The polyethylene compositions of the examples and comparative examples were subjected to cross fractionation chromatography (CFC) in the following manner. Then, the content ratio of the highly crystalline fraction eluted above 90 °C (TREF T≥90℃ ), the content ratio of the medium and low crystalline fraction eluted above 35 °C and less than 90 °C (TREF 35-90℃ ), and the soluble fraction eluted below 35 °C (TREF <35℃ ) were measured.
[0414] Cross Fractionation Chromatography (CFC) Measurement Conditions (including TREF and GPC-IR Analysis)
[0415] - Analytical equipment: Polymer Char CFC (detector: integrated detector IR5 MCT)
[0416] - Sample preparation and injection: 32 mg of the polyethylene composition was added to a 10 mL vial and placed in an autosampler. Then, 8 mL of 1,2,4-trichlorobenzene (TCB) was added, dissolved at 160 °C for 90 minutes, extracted after purging with nitrogen, and then injected into a temperature rising elution fractionation column (TREF column).
[0417] - Crystallization: After adjusting the temperature of the sample previously injected into the TREF column to 100 °C, cooling was carried out from 100 °C to 35 °C at 0.5 °C / min.
[0418] - Temperature Rising Elution Fractionation (TREF) Analysis: The previously crystallized sample was heated from 35°C to 125°C at intervals of 1°C and fixed. Then, the fractions eluted at each temperature within 25 minutes were analyzed. Specifically, it could be extracted and analyzed at 35°C for 25 minutes, then after increasing the temperature at intervals of 3°C, extracted and analyzed, and finally extracted and analyzed at 125°C for 25 minutes.
[0419] (6) Measurement of Tensile Properties of Polyethylene Composition
[0420] - Tensile strength, yield strength (MPa), 1% modulus, 2% modulus, elongation at break (%): Measured according to ASTM D 638 standard.
[0421] Specifically, at a temperature of 180°C and a pressure of 4500 lbf, the polyethylene composition was compression molded for 15 minutes to produce a sheet with a thickness of 1 mm, and then tensile specimens were prepared according to ASTM D 638 standard. According to ASTM D 638 standard, the specimens were subjected to a tensile test at a tensile rate of 500% / min at room temperature (25°C).
[0422] Here, the tensile strength and elongation at break respectively represent the strength and elongation at the break point obtained from the strength-elongation curve derived from the tensile test. The yield strength represents the strength at the yield point obtained from the strength-elongation curve derived from the tensile test. The 1% modulus and 2% modulus respectively refer to the initial modulus at 1% and 2% elongation obtained by calculating the tensile modulus from the starting point of the strength-elongation curve derived from the tensile test to 1% and 2% elongation.
[0423] [Table 2]
[0424]
[0425] [Table 3]
[0426]
[0427] As shown in Table 2 and Table 3, it was confirmed that compared with Examples 1 to 4, the polyethylene compositions of Examples 1 to 5 exhibited excellent mechanical properties. The polyethylene compositions of Examples 1 to 5 respectively contained the first ethylene-α-olefin copolymer and the second ethylene-α-olefin copolymer of the present invention with different densities and melt indices at a predetermined content ratio, and compared with Examples 1 to 4, they exhibited an increased high-crystallinity fraction (≥90°C elution ratio, TREF ≥90℃ ) and a decreased medium-crystallinity fraction (35 - 90°C elution ratio, TREF <35-90℃ ) and a soluble fraction (<35°C elution ratio, TREF <35℃) and exhibit increased yield strength and secant modulus (i.e., 1% and 2% initial modulus).
[0428] <Test Example 3: Preparation and Evaluation of Physical Properties of Polyethylene Films>
[0429] Polyethylene films were prepared from the polyethylene compositions prepared in the examples and comparative examples by the following blow molding process, and their physical properties were then measured and shown in Tables 4 and 5, respectively.
[0430] Preparation of Polyethylene Films
[0431] Blown films were prepared by inflation molding under the following equipment and conditions:
[0432] - Single screw extruder: Eugene Engineering Single Screw Extruder, Blown Film M / C, 50Phi, L / D = 32
[0433] - Extrusion temperature: 130 °C to 180 °C
[0434] - Die gap: 1 mm to 3 mm
[0435] - Blow-up ratio: 2.5
[0436] - Film thickness: 25 μm to 75 μm
[0437] Evaluation of Physical Properties of Polyethylene Films
[0438] - Haze (%): Measured according to ASTM 1003 standard.
[0439] - Tensile strength (MPa), 1% tensile modulus (MPa), 2% tensile modulus (MPa) and elongation at break (%): Measured in the MD / TD directions according to ASTM D 882 standard.
[0440] - Tear strength (N / mm): Measured in the MD / TD directions according to ASTM 1922 standard.
[0441] [Table 4]
[0442]
[0443] [Table 5]
[0444]
[0445] As shown in Tables 4 and 5, it is confirmed that, compared with Comparative Examples 1 to 4, the blown films prepared from the polyethylene compositions of Examples 1 to 5 of the present invention have excellent mechanical properties, high initial modulus and excellent stiffness while maintaining excellent printability, transparency, productivity and film processability.
Claims
1. A polyethylene composition comprising at least one ethylene-α-olefin copolymer, wherein, the polyethylene composition: The fraction of molecules eluting above 90 °C from the TREF analysis (TREF ≥90℃ ) is 55.0% or more, and The fraction of molecules eluted from the TREF analysis at temperatures above 35 °C and less than 90 °C (TREF 35-90℃ ) is 45% or less.
2. The polyethylene composition according to claim 1, wherein, the polyethylene composition: The density according to ASTM D 1505 is 0.925 g / cm 3 or more and 0.945 g / cm 3 or less, and has a melt index (MI) (190 °C, 2.16 kg load) according to ASTM D 1238 of 0.18 g / 10 min or more and 1.5 g / 10 min or less.
3. The polyethylene composition according to claim 1, wherein, the polyethylene composition: has a number average molecular weight (Mn) of 18,500 g / mol or more and 100,000 g / mol or less, a weight average molecular weight (Mw) of 100,000 g / mol or more and 500,000 g / mol or less, and a molecular weight distribution (Mw / Mn) of 1.0 or more and 10.0 or less.
4. The polyethylene composition according to claim 1, wherein, the polyethylene composition has a melting point (Tm) of 127 °C or more and 130 °C or less, a crystallization temperature (Tc) of 110 °C or more and 115 °C or less, and a crystallinity (Xc) of 50% or more and 70% or less.
5. The polyethylene composition according to claim 1, wherein, the polyethylene composition has a yield strength according to ASTM D 638 of 18 MPa or more.
6. The polyethylene composition according to claim 1, wherein, the polyethylene composition has a 1% modulus according to ASTM D 638 of 400 MPa or more and a 2% modulus according to ASTM D 638 of 330 MPa or more.
7. The polyethylene composition according to claim 1, wherein, the polyethylene composition comprises: (a) A first ethylene-α-olefin copolymer having a density of 0.930 g / cm 3 to 0.960 g / cm 3 and a melt index (MI 2.16 , at 190 °C and a load of 2.16 kg) of more than 0.05 g / 10 min; and (b) A second ethylene-α-olefin copolymer having a density of 0.870 g / cm 3 to 0.920 g / cm 3 and a melt index (MI 2.16 , at 190 °C and a load of 2.16 kg) of more than 15 g / 10 min; and wherein the polyethylene composition comprises an amount of (a) a first ethylene-α-olefin copolymer of 82% by weight or more and less than 100% by weight, and an amount of (b) a second ethylene-α-olefin copolymer of more than 0% by weight and 18% by weight or less.
8. The polyethylene composition according to claim 7, wherein, the (a) first ethylene-α-olefin copolymer: has a number average molecular weight (Mn) of 12,000 g / mol or more and 50,000 g / mol or less a weight average molecular weight (Mw) of 80,000 g / mol or more and 250,000 g / mol or less, and a molecular weight distribution (Mw / Mn) of 3.0 or more and 20.0 or less.
9. The polyethylene composition according to claim 7, wherein, the (a) first ethylene-α-olefin copolymer comprises an ethylene / 1-hexene copolymer.
10. The polyethylene composition according to claim 7, wherein, the (b) second ethylene-α-olefin copolymer: has a number average molecular weight (Mn) of 20,000 g / mol or more and 50,000 g / mol or less, a weight average molecular weight (Mw) of 50,000 g / mol or more and 100,000 g / mol or less, and a molecular weight distribution (Mw / Mn) of 1.5 or more and 4.0 or less.
11. The polyethylene composition according to claim 7, wherein, the (b) second ethylene-α-olefin copolymer comprises an ethylene / 1-octene copolymer.
12. A polyethylene film, which comprises the polyethylene composition according to claim 1.
13. The polyethylene film according to claim 12, wherein the MD / TD average 1% modulus of the polyethylene film is 450 MPa or more according to ASTM D 882, and the MD / TD average 2% modulus is 350 MPa or more according to ASTM D 882.
Citation Information
Patent Citations
Appararus for checking residue of bottom thread and System for checking residue of bottom thread using the same
KR1020220144633A
A Shellfish Seed Net Input Apparatus
KR1020220170467A
Skin whitening composition comprising bioconversion product of Rubia akane callus extract as an active ingredient
KR1020230150130A